Drought weakens greenhouse gas sink of global wetlands - Longxin Qiao; Xinxin Wang; Hongyang Chen; Jihua Wu; Xiangming Xiao; Ming Nie; Rui-Ting Ju; Yuhan Zheng; Xi Zhang; Qiang He; Xutong Ru; Lijuan Cui; et al. (Environmental Impact Assessment Review, 2027)

Level terraces enhance the vertical distribution of soil organic carbon in mixed forests: microbial mechanisms and carbon fraction dynamics on the loess plateau - Zhe Li; Ning Zhang; Zi-ming Wang; Rui-kun Feng; Yi-qiao Chen; Zheng-hua Liu; Wen-fan Wang; Jia-bin Liu; Jian Wang (CATENA, 2026)

Engineering Naematelia aurantialba as a Robust Synthetic Biology Chassis: Stable Episomal Vector Construction and Metabolic Optimization for Enhanced Polysaccharide Synthesis - Yuhang Ma; Yingfeng Wang; Ming Zhang; Liang Sun; Rui Wang; Yian Gu; Peng Lei; Hong Xu (Bioresource Technology, 2026)

Experimental and numerical study of diaphragm in-plane stiffness on the seismic performance of building structures with DCPCF - Yuan-yuan Sun; Rui Pang; Shu-ting Liang; Yi-ming Wen; Chun-lin Wang (Engineering Structures, 2026)

Viscoelastic response of composite tensile armor layers in flexible risers under axial random loading - Rui Bao; Chen An; Ming Wang; Yu Zhang; Changyun Li (Ocean Engineering, 2026)

How elevated-road design and adjacent building configuration shape vertical exposure to traffic-related particles in dense urban environments - Ruhui Cao; Yunlu Wang; Rui Xu; Ming Cai; Yonghong Liu; Zhanyong Wang (Landscape and Urban Planning, 2026)

Oxidized Late Devonian arc intrusion in the Jiangda area, eastern Tibet: Implication for heterogeneous porphyry Cu-Au fertility of Paleo-Tethyan arc magmas - Rui Ma; Ming-Liang Huang; Lei-Luo Xu; Jing-Jing Zhu; Bao-Di Wang; Hong-Rui Zhang; Rui-Zhong Hu; Xing-Chun Zhang; Xian-Wu Bi (Journal of Asian Earth Sciences, 2026)

Predicting and optimizing pyrolysis behaviors of Shendong coal macerals (vitrinite & inertinite) swelled by single and mixed solvents with machine learning - Linyang Wang; Qiuxiang Yao; Duo Ma; Rui Cao; Xinzhuang Yao; Ming Sun (Fuel, 2026)

Waste akebiae trifoliata-derived WO3 hierarchical tubes efficient detection of ppb-level triethylamine gas at low temperature and application in food freshness detection - Wen-Xiao Li; Jia-Wang Wang; Rui-Long Li; Qiu-Yue Zheng; Bao-Yu Song; Bo-Ya Liu; Li-Xia Zhao; Ying Fu; Ying-Ming Xu (Chemical Engineering Journal, 2026)

Sustainable valorization of agricultural waste into high-value aromatics via an integrated chemo-enzymatic strategy - Fang Gao; Shike She; Yaxin Wang; Mengyao Hao; Ming Wu; Yacheng Cao; Dong Zhu; Liping Shi; Liang Zhang; Rui Zhu (Biomass and Bioenergy, 2026)

A lyophilized RPA–CRISPR/Cas13d one-pot platform for rapid detection of porcine circovirus type 3 - Li-Na Shao; Zheng-Luo; Bao-Ling Liu; Tong-Xu; Yuan-Meng Wang; Jia-Qi Duan; Lei-Zhao; You-You Li; Yang-Ming Dai; Qin-Rui Jia; Le-Yi Zhang; Ling-Zhu; et al. (Analytica Chimica Acta, 2026)

Kosakonia oryziphila KC516 mediated growth promotion of Cosmos bipinnatus in phosphogypsum by modulating rhizosphere geochemistry and root transcriptome - Jing Zhang; Hao-Tian Dong; Yuan-Chun Yang; Rui Liu; Shuai Wang; Ao-Li Zhang; Yuan Su; Ming-Hua Dong; Yan-Ru Cao; Hua-Li Zhang (Environmental Geochemistry and Health, 2026)

Prevalence and risk factors of bovine tuberculosis in dairy cattle, 2020–2025: A systematic review and meta-analysis of available literature - Qi Wang; Xiao-Nan Wang; Xiao-Qun Liu; Long-Ge Zhao; Zi-Tong Jing; Tian Tian; Jia-Ting Zhang; Yi-Xing Zhao; Jian-Ming Li; Nai-Chao Diao; Kun Shi; Rui Du (Preventive Veterinary Medicine, 2026)

Corrigendum to “TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy” [J Hazard Mater 494 (2025) 138515] - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2026)

Exploring the mechanism of platycodon grandiflorum saponins in treating Mycoplasma pneumoniae pneumonia based on intestinal microbiota and metabolomics - Rui Shuang Ji; Yun Fei Yang; Chan Yu Wu; Zhen Jing Yang; Jin Zhao Du; Jing Huang Fu; Lin Yao; Wei Ming Wang (Food Bioscience, 2026)

Autophagy-augmenting peptide nanoplatform for synergistic chemo-immunotherapy against breast cancer - Chen Wei; Wei Gao; Xingyue Li; Ming Fu; Fantao Lin; Xiaoyu Zhao; Huiying Jia; Kang Zhang; Changgang Sun; Rui Wang; Jingkun Bai (Chemical Engineering Journal, 2026)

Oxygen demand and behavioral responses of adult largemouth bass (Micropterus salmoides) to intensive aquaculture-related drivers - Hao Fan; Chang Guo; Xiang Lei; Peng Wan; Ming Zhu; Deqing Wang; Rui Song (Aquacultural Engineering, 2026)

Hydrogel-encapsulated microalgae-bacteria consortia for resilient saline agriculture - Xiao-Jing Wang; Nan Wu; Xiao Yu; Si-Ming Li; Zi-Rui Yang; Zhi-Hai Zhong; Kang Wang; Hong-Li Cui; Cheng-Gang Ren; Song Qin (World Journal of Microbiology and Biotechnology, 2026)

One novel sesquiterpenoid from the fungus Pestalotiopsis clavata JSQ 12 isolated from the mushroom Lanmaoa asiatica - Zi-Lin Wang; Shuai-Ming Zhu; Yu Yang; Rui Xu; Xue Zhao; Chen Sun; Qian Luo; You-Zhi Zhang; Guo-Gang Zhang; Chang-Wei Li (Natural Product Research, 2026)

Dimefluthrin-induced multigenerational endocrine toxicity in zebrafish (Danio rerio) offspring via parental exposure - Wei-Guo Wang; Rui-Rui Li; Ming-Jun Yang; Jing-Ying Hu; Wen-Ping Xu; Li-Ming Tao; Yang Zhang (Pesticide Biochemistry and Physiology, 2026)

A study on the hydrodynamic performance and wake modulation effect of a twisted pre-swirl stator in a rim-driven thruster - Yi-Ming Hu; Cong Sun; Min Liu; Chun-Yu Guo; Pei-Rui Tang; Yu Zhao; Chao Wang (Ocean Engineering, 2026)

MFN2-mediated remodelling of ER-mitochondria communication alleviates ochratoxin A-induced hepatocyte ferroptosis by enhancing mitophagy - Zi-Yan Hu; Rui-Qi Liu; Yu-Xuan Ouyang; Ming-Shan Chen; Jia-Xin Wang; Ming Lou; Yi-Feng Huang; Hong-Li Si; Fu-Wei Jiang; Zhuo-Yu Liu; Yi-Bo Wang; Li Wang; et al. (Journal of Hazardous Materials, 2026)

Effective photodynamic inactivation of curcumin in combination with ethylenediaminetetraacetic acid against Burkholderia gladioli pathovar cocovenenans - Xiu-Xia Tian; Jia-Jun Yan; Rui Huang; Quan Zhou; Qi-Ying Zeng; Yu-Ming Jiang; Zi-Hui Chen; Hai-Yan Wang; Bai-Sheng Li; Yong-Ning Wu; Wei-Liang Wu (Food Research International, 2026)

Strip deep rotary tillage reduces the optimal nitrogen rate for high maize yield in the North China Plain: A system-specific optimization of root-shoot growth and soil nitrogen availability - Zhuohan Gao; Hongliang Lan; Zhigang Wang; Xinbing Wang; Zaisong Ding; Rui Wang; Lu Liang; Congfeng Li; Ming Zhao; Baoyuan Zhou (Field Crops Research, 2026)

Analysis of Arbuscular Mycorrhizal Fungal Community in Soil of Sugarcane at Different Tillage Depths - Qun-Qing Huang; Sheng Wang; Ying-Jie Nong; Kai-Mao Zhong; Yi-Cheng Su; Xiao-Juan Qin; Jin-Lian Zhang; Yi-Hao Kang; Ting-Su Chen; Shi-Yuan Zeng; Xi-Chao Deng; Ming-Guo Jiang; et al. (Sugar Tech, 2026)

Histamine regulation in shaping spindle refractoriness: a computational modeling study - Bo Wang; Qiang Li; Wen-Hua Wang; Wan-Rong Zan; Yi-Ming Li; Jiang-Ling Song; Rui Zhang (Journal of Computational Neuroscience, 2026)

Research trends in COPD–associated invasive pulmonary aspergillosis over the past two decades: a bibliometric and topic modelling analysis - Xiaowen Wu; Rui Wang; Jing Tan; Jiaxiang Li; Zhiyue Yu; Ming Gao; Limei Geng (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Prevotella copri impairs bone mass via osteoclast activation in mice - Rui Li; Haiyan Zhang; Shiyong Xin; Tiantian Zeng; Wenchu Qian; Yawen Sun; Yunfei Cao; Yuxin Wang; Bin Li; Ming Tian; Hai Lin; Haifang Li (Molecular and Cellular Biochemistry, 2026)

How to make big data accessible to plant biologists and beyond: Ten years of lessons from TBtools - Junting Feng; Chengjie Chen; Ya Wu; Longjiang Fan; Zhang Zhang; Ming Chen; Haibao Tang; Guangchuang Yu; Jian Ren; Jingchu Luo; Yi Liao; Aiping Luan; et al. (Molecular Plant, 2026)

Os79, a UDP‐Glycosyltransferase, negatively regulates cadmium tolerance and accumulation in rice - Rui Guo; Hao Yu Wang; Chong Wei Zhong; Rong Rong Ma; Jiu Huang; Jin Chen; Xian Jiao Guan; Lu Zheng; Ren Fang Shen; Ming Qing Liu; Xiao Fang Zhu (Journal of Hazardous Materials, 2026)

A new pathway to enhance the oceanic carbon sink: inorganic carbonate precipitation driven by calcium–alkali coupling - Shan Shan Liu; Jin Ming Song; Xue Gang Li; Hua Mao Yuan; Li Qin Duan; Jun Lei Li; Bao Xiao Qu; Qi Dong Wang; Jun Ma; Jian Wei Xing; Zhi Bo Wang; Rui Wang; et al. (Journal of Environmental Management, 2026)

High-efficiency integration of capacitive deionization and electricity generation in single cycle enabled by basswood-derived free-standing carbon electrode - Yao Qiu; Rui Zhang; Shuyu Kong; Yishuo Teng; Dongling Li; Ming Hou; Jingwen Wang; Yongzhao Hou; Guangwu Wen; Dong Wang (Desalination, 2026)

A Lepidoptera Synthesis Phylogeny of 11,001 Species and Its Application in Phylogenetic Profiling of Herbivore DNA Barcodes: Towards an Integrative Phylogenetic Framework for Insects - Douglas Chesters; Ming‐Qiang Wang; Perttu Anttonen; Jing‐Ting Chen; Rui Cheng; Yi Li; Arong Luo; Michael C. Orr; Tingting Xie; Qingsong Zhou; Chao‐Dong Zhu (Zoologica Scripta, 2026)
We herein constructed a phylogeny of Lepidoptera synthesizing multiple information types, a phylogenomics backbone, a multigene supermatrix with species‐comprehensive DNA barcodes, and topological information from a compiled database of standardized machine‐readable trees from over 100 previous studies. We then applied the new phylogenetic synthesis as a profiling framework for a large DNA barcode dataset of caterpillars from a tree diversity experiment. The synthesis phylogeny comprised 11,001 species. Phylogenetic information content was taxonomically skewed towards butterflies (i.e., Nymphalidae, Papilionidae and Pieridae), and parts of Macroheterocera (Geometridae, Sphingidae, Saturniidae and Bombycidae), while undersampling of Lepidoptera species diversity was present in Erebidae, Noctuidae, Gelechioidea and Pyraloidea. Caterpillar Phylogenetic Diversity (PD) increased with tree richness in the diversity experiment regardless of processing choices in calculating caterpillar PD, including whether calculated on plot OTU alone, plot OTU placed onto a simple reference phylogeny or plot OTU placed to the comprehensive reference phylogeny. Stronger correlations between tree diversity and uncorrected Faith's PD of caterpillars were observed where OTU were placed onto the full reference tree, and where long branch OTU were removed prior to PD calculation, though no significant differences in the strength of the tree diversity effect across context and processing choice were observed for standardized PD. In calculation of plot‐level PD, focus should remain on community sample size, with the results herein supporting the use of any available reference phylogeny as context, though correspondence of PD indices to environmental gradients might be stronger where plot OTU can be placed to a comprehensive reference phylogeny. The phylogeny presented herein enables inference of varied evolutionary information for Lepidoptera DNA barcode sets.

Centralized mechanical e-waste dismantling is associated with lower farmland soil heavy metal pollution and carbon emission intensity - Yu Zhang; Ming-jiang He; Wei-jun Fu; Jie Wang; Ke-li Zhao; Xiang-rui Xu; Ji-zi Wu (Journal of Environmental Chemical Engineering, 2026)

Theta-aurora dynamics: Ionospheric mapping of evolving magnetospheric plasma boundaries - Xin-Ming Chen; Zan-Yang Xing; Qing-He Zhang; Yong-Liang Zhang; Hui-Gen Yang; L. R. Lyons; K. Oksavik; S. E. Milan; Rui-Long Guo; Tong Xu; Bin-Bin Tang; Xiang-Yu Wang; et al. (Science China Earth Sciences, 2026)
The theta-aurora, an auroral feature bridging the nightside and dayside auroral oval under a northward interplanetary magnetic field (IMF), is closely linked to the energetic plasma evolving within the magnetosphere. While existing views emphasize that energetic plasma resides on closed field lines, the mechanism by which it is accelerated and precipitates on open field lines to form the theta aurora remains poorly understood. Here, we introduce a mechanism derived from multi-instrument observations of theta-aurora evolution in the Northern Hemisphere and simulations conducted using a global magnetohydrodynamics (MHD) model. The observations and simulations exhibit excellent agreement, revealing that the theta-aurora represents ionospheric projections of boundaries between distinct magnetospheric plasma. These different magnetospheric plasma, an energetic structure originating from the plasma sheet and the preexisting cold lobe plasma, develop a boundary with contrasting physical properties that drive localized plasma instabilities. Particle precipitation occurs at plasma boundary, and controls both the formation and temporal evolution of theta-aurora. Our findings provide critical insights into the coupling between the ionosphere and magnetosphere under northward IMF.

Improved eradication of apple stem grooving virus and apple chlorotic leaf spot virus in apple rootstocks by combining thermotherapy with electrotherapy - Xiao-Yan Ma; Qing Li; Zhi-Wei Kang; Ming-Yuan Jing; Ya-Ting Zhang; Min-Rui Wang; Dong Zhang; Lu Bao; Juan-Juan Ma (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Decoding the flavor formation mechanism of the functional microbial community in koji-mediated fish sauce - Jin-Xiu Xu; Xin Zhang; Bai-Feng Fu; Zhao-Rui Li; Min-Bo Li; Zhen-Yu Wang; Xian-Bing Xu; Shu-Zhen Cheng; Ming Du (Food Bioscience, 2026)

The light side of the microbiome in trauma: Mechanism and applications - Han-Yue Luo; Lei-Ming Cao; Kan Zhou; Yi-Fu Yu; Yao Xiao; Guang-Rui Wang; Bing Liu; Qiu-Ji Wu; Xiao-Long Wang; Zhi-Yong Song; Lin-Lin Bu (Chemical Engineering Journal, 2026)

Image restoration of sediment particles in turbid environments based on a multi-scale fusion algorithm - Xiaolong Ma; Ming Bai; Yiteng Wang; Rui Xu; Sheng Li; Houzhen Wei (Journal of Soils and Sediments, 2026)

Hydrothermal-responsive plasmonic aerogel for dynamic 3D hotspot regulation and ultrasensitive SERS detection of dairy products contaminants - Jing-Xiang Wang; Zhi-Gao Xu; Xin-Rui Wang; Yao-Yao Zhang; Ri-Hui Su; Xin-Xin Zhang; Su-Ming Dai; Wei-Wei Zhu; Xue-Cai Tan; Ke-Jing Huang; Jun Yan (Analytica Chimica Acta, 2026)

Effects of suspended sediment on the survival and settlement of Crassostrea ariakensis and Crassostrea sikamea larvae: Results from lab experiments - Nan-nan Li; Yu Han; Yuan-ge Chen; Wei-liang Dong; Long-ling Ouyang; Rui-liang Fan; Wei Jiang; Jia-feng Fang; Nian Wei; Jin-ming Wang; Wei-min Quan; Jian Zeng (Regional Studies in Marine Science, 2026)

Thioredoxin PgTRX acts as a protein elicitor to suppress green mold in citrus fruit via modulation of glutathione metabolism - Rong Zhu; Ou Chen; Yao Xu; Rui Huang; Wenjun Wang; Jian Ming; Kaifang Zeng (Postharvest Biology and Technology, 2026)

Insight into the enhancement effect of pristine and amino-functionalized MWCNTs@SiO2 on the CO2 absorption and solar-driven regeneration performance of alkaline deep eutectic solvent based nanofluid system - Wei Wang; Yang Tang; Yi-Ming Chen; Rui-Rui Zhou; Zhang-Mao Hu; Jin-Cheng Huang (Journal of Environmental Chemical Engineering, 2026)

Effective recovery of Dy from LiCl-KCl molten salt via controlled potential on Ga electrode: Mechanism, kinetics and thermodynamics of electrode reaction - Yuying Xiao; Wenlong Li; Rui Li; Ziqin Huang; Ming Gong; Jiandong Li; Ji Wang; Lifeng Chen; Shunyan Ning; Xiangbiao Yin; Wei Han; Yuezhou Wei (Journal of Environmental Chemical Engineering, 2026)

An earthworm-inspired hydrogel coating for hydration-assisted aqueous lubrication on diverse polymer substrates - Zhi-Guo Wang; Xi Liao; Yong-Jie Dan; Yu-Wei Liu; Yan-Hua Niu; Rui Hong; Ming Cai; Ju-Xiang Gou; Jia-Zhuang Xu; Zhong-Ming Li; Ka Li (Chemical Engineering Journal, 2026)

Spatiotemporal relationships between mammal habitat suitability and recreational hiking intensity in Xiaowutaishan National Nature Reserve, China - Ming Yam Chan; Yue Cao; Zhicong Zhao; Pei Wang; Yunshuang Feng; Le Yu; Steve Carver; Xuehua Liu; Ruijia Zhu; Fengze Lin; Xialin Li; Yiqing Wang; et al. (Biological Conservation, 2026)

Unpacking asthma risks: A multi-level spatial analysis of social determinants of health in the U.S. - Ming Yan; Cong Fu; Xiao Huang; Siqin Wang; Yuchen Li; Lambed Tatah; Rui Zhu; Yanqing Xu (Applied Geography, 2026)

Who is the best allogeneic hematopoietic stem cell transplant donor for severe aplastic anemia? Data from the Chinese Bone Marrow Transplantation Registry Group (CBMTRG) - Zheng-Li Xu; Lan-Ping Xu; Shun-Qing Wang; De-Pei Wu; Xi Zhang; Su-Jun Gao; Ling-Hui Xia; Rui Xi; Jian-Min Yang; Qi-Fa Liu; Ming Jiang; Xiao-Sheng Fang; et al. (Science Bulletin, 2026)

Macro-micro scales insights into the effect of enrofloxacin on the Fe-C-Anammox system: Performance enhancement, metabolic optimization, and ARGs reduction - Rui Zhong; Jiaqi Lu; Liping Xie; Xiao-Ming Ji; Qi Zhang; Xiao Ma; Wenru Liu; Ying Wang (Journal of Water Process Engineering, 2026)

Twinned structure–enhanced S-scheme heterojunction in Zn0.8Cd0.2@g-C3N4 for efficient CO2 photocatalytic reduction - Ming-yang Liu; Hao-wen Zhu; Qing-shan Wang; Cong Liu; Heng-fei Cui; Jun-ying Tang; Rui-tang Guo (Fuel, 2026)

Effect of roasting on the chemical profiles of white and black sesame seeds during accelerated storage - Hao Liu; Shu-Guang Gao; Ming-Zhe Sun; Mei-Qi Yang; Huai-Yang Cao; Ke-Xin Zhang; Min-Shu Hong; Rui-Fu Cui; Zhao Qin; Hua-Min Liu; Xue-Ya Wang; Zhi-Jie Li (Food Chemistry, 2026)

Cytoplasmic-nuclear remote suppression of c-MYC induces cell cycle arrest and enhances radiotherapy sensitivity in liver cancer via biohybrid platelets - Lin Xiao; Fei Ge; Qinyu Ji; Rui Ji; Yan Wang; Shaoqing Ju; Ming Cui; Donglin Xia; Rongrong Jing (Chemical Engineering Journal, 2026)

In-situ cultivation and process dynamics of algal-bacterial granular sludge in a continuous-flow self-circulation reactor - Wei-Kang Qi; Yu-Ge Sun; Ming-Ming Zhang; Rui Hu; Yong-Zhen Peng; Cong Wang (Bioresource Technology, 2026)

Correction to: Genetic Mapping of the Wheat Dimeric α-Amylase Inhibitor Multi-Gene Family Using Allele-Specific Primers Based on Intergenomic SNPs - Ji-Rui Wang; Yu-Ming Wei; Ze-Hong Yan; You-Liang Zheng (Plant Molecular Biology Reporter, 2026)

Exogenous melatonin alleviates heat stress-induced metabolic slowdown affecting broiler growth by improving lipid metabolism - Fei Song; Binglin Wang; Xin Kang; Aige Han; Huiyuan Rui; Xiangyang Xu; Yi Guo; Ming Ge; Xiaowen Jiang; Wenhui Yu (Journal of Thermal Biology, 2026)

Gastrin releasing peptide receptor antagonism in the paraventricular nucleus exerts antihypertensive effects in 2K1C rats - Xiao-Min Wang; Jin-Jun Liu; Yi-Pu Wang; Chao Bai; Abdoulaye Issotina Zibrila; Wen-Jie Xia; Rui-Na Yang; Yu-Ming Kang; Xiao-Jing Yu (Toxicology and Applied Pharmacology, 2026)

Sunlight-driven evolution of the aroma profile in fish sauce fermentation - Jin-Xiu Xu; Xin Zhang; Bai-Feng Fu; Zhao-Rui Li; Min-Bo Li; Zhen-Yu Wang; Xian-Bing Xu; Shu-Zhen Cheng; Ming Du (Food Bioscience, 2026)

Dietary Haematococcus pluvialis powder enhances the growth and hepatopancreas and intestinal health of Leuciscus waleckii via NF-κB/Nrf2 pathway - Bei Xi; Tong-Tong Tan; Qi Sun; Ming-Xuan Zhang; Jia-Jing Wang; Rui Zhu; Deng-Lai Li; Li-Fang Wu (Fish & Shellfish Immunology, 2026)

Construction of bonded CoAl-LDH/COF-316 hybrid photocatalysts with Z-scheme heterojunction for efficient reduction of diluted CO2 - Chao Fan; Rui-Yao Li; Can-Can Yu; Ya Wang; Yu-Xin Xie; Nan-Nan Zhang; Lu-Hua Shao; Gui-Ling Zhang; Hong Dong; Feng-Ming Zhang (Chemical Engineering Journal, 2026)

Performance of heavy metals in the intertidal zone surface sediments of the Yellow River Estuary under water-sediment regulation scheme - Shan Shan Liu; Jin Ming Song; Xue Gang Li; Hua Mao Yuan; Li Qin Duan; Jun Ma; Feng Min Pan; Jian Wei Xing; Chen Long Feng; De Tong Tian; Zhi Bo Wang; Rui Wang (Marine Pollution Bulletin, 2025)

Editorial: Crust formation from subduction to collision - Rui Wang; Ming Tang; Qing Wang; Kang Chen; Peter A. Cawood (Lithos, 2025)

Precise construction of Anderson-type polyoxometalate-based covalent organic frameworks for photocatalytic hydrogen peroxide production - Zhang-Di Liu; Zai-Xiang Zhang; Yang Yang; Rui Xing; Zi-Hao Wei; Hou-He Liu; Jiang-Bo Ming; Jin Zhu; De-Yin Wang (Journal of Water Process Engineering, 2025)

Highly efficient, selective, and sustainable adsorption of Nd3+ ion by amino-phosphonic acid functionalized polyacrylonitrile fibers via surface synergistic coordination - Xiao-Wei Zhang; Shuang Wang; Feng Guo; Jin-Xiu Wu; Yan-Hong Hu; Ming-Guang Chen; Rui-Lin Ren (Journal of Environmental Chemical Engineering, 2025)

Effects of pressing temperature on selenium speciation, volatile profiles, and sensory evaluation in selenium-enriched rapeseed oils - Ming Chen; Jingyi Wang; Wangting Zhou; Zhenzhou Zhu; Jingren He; Rui Zhang; Muci Wu (Food Research International, 2025)

Corrigendum to “Porphyrinized carbon quantum dots: A novel antibacterial nanomaterial for visualized and broad-spectrum treatment of drug-resistant infected wounds” [Chem. Eng. J. Volume 522, 15 October 2025, 166981] - Mengwei Zhang; Jingjing Ye; Jingyao Zhang; Zijian Tian; Lebin Gan; Qiang Wang; Rui Li; Diya Sun; Zishuo Pei; Ming Li; Minghui Liang; Tianbing Wang (Chemical Engineering Journal, 2025)

Cryogenic pre-activation induces structural optimization and performance boost for Li-rich Mn-based cathodes - Rui-Chi Li; Lan-Fang Que; Jun-Sen Jiang; Fu-Da Yu; Ji-Huai Wu; Xuan Wang; Can-Zhong Lu; Yi-Ming Xie (Chemical Engineering Journal, 2025)

Chemical constituents of Tinospora hainanensis and their chemotaxonomic significance - Ming-Hua Wang; Rui Ao; Bao-Qiang Liu; Juan Zhang; Jun-Sheng Zhang (Biochemical Systematics and Ecology, 2025)

Comparative analysis of sexual dimorphism in ultrastructure of sensilla on antennae, frons, and compound eyes of Azpeytia shirakii Hurkmans (Diptera: Syrphidae) - Bin Mao; Yu-Hui Cong; Ming-Hui Wang; Han-Rui Ren; Yun-Li Xiao (Zoomorphology, 2025)

Temporal transcriptomics reveal crucial networks underlying jasmonate-mediated diurnal floret opening and closure in rice - Rui Zhang; Xiaohui Xi; Xiaozhou Hu; Dan Xiang; Yi Wang; Yu Pan; Xi He; Yuhan Zhang; Lilan Hong; Yuanzhu Yang; Ming Zhou (Science China Life Sciences, 2025)

CRP and HNF1A collaborate to regulate the progression of laryngeal cancer through the Wnt signaling pathway - Zhigang Zhao; Xiaojing Zhu; Jinyuan Xu; Penglong Song; Yanan Sun; Zhenming Yang; Li Wang; Jiarui Zhang; Rui Zhao; Xiaoxue Chen; Wenjing Li; Linli Tian; et al. (Functional & Integrative Genomics, 2025)

Two undescribed constituents from Salvia castanea Diels and evaluation of their cytotoxic activity - Rui Zhang; Dong-Dong Wang; Lian-Yu Tang; Tashi Tsering; Jing-Ming Jia; An-Hua Wang (Natural Product Research, 2025)

Stress migration and failure mechanisms of rocks with holes under gradient stress conditions - Xingyu Wu; Ming Tao; Zheng Yang; Ziheng Xiao; Rui Zhao; Shaofeng Wang (International Journal of Rock Mechanics and Mining Sciences, 2025)

Quantifying transverse gradient effects on hydrological connectivity and optimal thresholds in the lower yellow river floodplain - Liyu Quan; Gaoxu Wang; Rui Shi; Daiyuan Li; Chaojie Niu; Ming Li; Caihong Hu (Geomorphology, 2025)

Fe3+ modulated protein-based soft actuators for organic solvent working conditions: Spatiotemporal programmability, multi-terrain locomotion, self-sensing and full biodegradability - Shaorong Zong; Xiaohui Chu; Jia Kang; Cungang Gao; Pengxin Jia; Yue Sun; Ming Zhang; Kaiming Wang; Rui Nian; Wenfa Yu (Chemical Engineering Journal, 2025)

Stream sediment geochemical anomaly identification and mapping in the Xinbo area, northern China: Using a catchment basin approach and the Apriori algorithm - Ming Liang; Panfeng Liu; Rui Tang; Xiaodong Wang; Chao Li; Feng Zhu (Applied Geochemistry, 2025)

Marine Hydrogen Pressure Reducing Valves: A Review on Multi-Physics Coupling, Flow Dynamics, and Structural Optimization for Ship-Borne Storage Systems - Heng Xu; Hui-Na Yang; Rui Wang; Yi-Ming Dai; Zi-Lin Su; Ji-Chao Li; Ji-Qiang Li (Journal of Marine Science and Engineering, 2025)
As a zero-carbon energy carrier, hydrogen is playing an increasingly vital role in the decarbonization of maritime transportation. The hydrogen pressure reducing valve (PRV) is a core component of ship-borne hydrogen storage systems, directly influencing the safety, efficiency, and reliability of hydrogen-powered vessels. However, the marine environment—characterized by persistent vibrations, salt spray corrosion, and temperature fluctuations—poses significant challenges to PRV performance, including material degradation, flow instability, and reduced operational lifespan. This review comprehensively summarizes and analyzes recent advances in the study of high-pressure hydrogen PRVs for marine applications, with a focus on transient flow dynamics, turbulence and compressible flow characteristics, multi-stage throttling strategies, and valve core geometric optimization. Through a systematic review of theoretical modeling, numerical simulations, and experimental studies, we identify key bottlenecks such as multi-physics coupling effects under extreme conditions and the lack of marine-adapted validation frameworks. Finally, we conducted a preliminary discussion on future research directions, covering aspects such as the construction of coupled multi-physics field models, the development of marine environment simulation experimental platforms, the research on new materials resistant to vibration and corrosion, and the establishment of a standardized testing system. This review aims to provide fundamental references and technical development ideas for the research and development of high-performance marine hydrogen pressure reducing valves, with the expectation of facilitating the safe and efficient application and promotion of hydrogen-powered shipping technology worldwide.

Inverse design of three-dimensional electrocatalytic oxidation process for water purification via machine learning and DFT-based descriptors - Linjin Li; Qiyao Wang; Yaoze Wang; Guangfei Qu; Yingying Cai; Rui Xu; Ming Jiang; Nanqi Ren (Process Safety and Environmental Protection, 2025)

SIRT3 promotes mitophagy to attenuate fumonisin B1-induced chicken hepatocyte senescence and antagonism of lycopene - Yuan-Hang Chang; Ming-Shan Chen; Hong-Mei Zhu; Rui-Qi Liu; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yue Cheng; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Scale effects on buffeting response of long-span bridges - Yi Su; Mingshui Li; Jin Di; Rui Sun; Ming Li; Fengjiang Qin; Yan Jiang; Jie Wang (Engineering Structures, 2025)

Multi-scale analysis of the influence of red-bed lithological interface on tunnel deformation and instability - Jing-Kai Qu; Yi-Guo Xue; Fan-Meng Kong; Cui-Ying Zhou; Zhen Liu; Zuo-Peng Wang; Jin-Rui Duan; Yan Ai; Zi-Ming Qu; Jian-Ning Wang; Bo Wang; Chao Lu; et al. (Engineering Geology, 2025)

Sunlight-activated photochromic-photothermal nanofibrous textiles for self-monitored thermal management - Shuai Liang; An-Yang Duan; Shi-Kun Yan; Yan-Rui Zhao; Jin Zhang; Guo-Wei Xiao; Chang-Hai Xu; Ji-Xiang Hu; Guo-Ming Wang (Chemical Engineering Journal, 2025)

Halogen-sulfur synergy in benzodithiophene-benzodithienedione conjugated polymers: Molecular design of high-performance photoelectrodes for metal anti-corrosion - Rui Ding; Jin-ying Li; Yi-wen Zhang; Hao-han Cao; Xiao Liu; Yu-han Wang; Ming-di Lei; Yu-lin Zhang; An-lan Ji; Yu-chen Zhang; Jie Liu; Tai-jiang Gui; et al. (Chemical Engineering Journal, 2025)

In/S co-decorated SnSe encapsulated in a dual carbon layer for sodium ion storage - Ya Ru Pei; Yong Jin Xia; Lei Ming Wang; Rui Li; Jun Xi Peng; Xue Jing Yang; Jian Li; Chun Cheng Yang; Qing Jiang (Chemical Engineering Journal, 2025)

Porphyrinized carbon quantum dots: A novel antibacterial nanomaterial for visualized and broad-spectrum treatment of drug-resistant infected wounds - Mengwei Zhang; Jingjing Ye; Jingyao Zhang; Zijian Tian; Lebin Gan; Qiang Wang; Rui Li; Diya Sun; Zishuo Pei; Ming Li; Minghui Liang; Tianbing Wang (Chemical Engineering Journal, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Associations Between Pre- and Post-Diagnosis Dietary Inflammatory Patterns and Ovarian Cancer Survival: Results From the Ovarian Cancer Follow-Up Study - Jia-Xin Liu; Rui-Han Bao; Meng Luan; Chuan Liu; Lang Wu; Fang-Hua Liu; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Qian Xiao; Dong-Hui Huang; Xiao-Ying Li; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Reconstructing the tectonic evolution of the Mudanjiang Ocean: Metamorphic insights from the Heilongjiang Complex, NE China - Guang-Ming Sun; Xu-Ping Li; Hans-Peter Schertl; Jin-Rui Zhang; Xiao Wang; Wen-Yong Duan (Journal of Asian Earth Sciences, 2025)

Integration of human sensory evaluation, intelligent E-tongue/E-nose systems, microbiomics, and metabolomics to comprehensively analyze flavor characteristics and dietary improvement mechanisms of processed Buddha's hand fruit - Zi-Xuan Ding; Yue-Hua Chen; Jia-Nuo Zhang; Wen-Yu Wang; Xin-Ru Zhang; Rui-Bo Sun; Hui Zhang; Ming Xie; Hui-Peng Song (Food Bioscience, 2025)

Chinese Tuina ameliorates muscle damage by regulating endoplasmic reticulum stress and autophagy in a rat model of skeletal muscle contusion - Hai-chao Liu; Hao-ming Zhu; Ming Li; Bo-rui Chen; Zheng-yu Yang; Yu Wang; Shi-zhong Wang; Shao-qing Chen; Jian-ping Lin (Tissue and Cell, 2025)

The ultrastructure of the Cretaceous feathers highlights the evolution of the feather - Jiajia Wang; Rui Qiu; Qian Chen; Di Liu; Tongbo Zhang; Ying Li; Xinjun Zhang; Baopeng Wang; Dongyu Hu; Dong Ren; Xiaolin Wang; Xiaofei Xia; et al. (Science Bulletin, 2025)

TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Functional nucleic acid-stabilized selenium nanotechnology enable synergistic healing of diabetic chronic wounds - Si-Wei Yang; Jing Wang; Yan Tan; Xiao Jing; Chen-Yu Wang; Zhi-Li Yao; Wen-Hui Wang; Yong-Ji Li; Hao-Rui Li; Yan Zhao; De-Ming Kong; Qi-Liang Cai (Chemical Engineering Journal, 2025)

Catalytic phase transition of cobalt oxide enriched in mesoporous carbon polyhedrons for electrosorption of molybdate oxyanions - Yu-Jen Shih; Zhi-Lun Wu; Ming-Rui Wang; Chin-Pao Huang (Chemical Engineering Journal, 2025)

Drivers of ecosystem service trade-off changes in different climate zones: a case study of the Sichuan–Yunnan–Loess plateau ecological shelter, China - Hao-Rui Li; Shuai Ma; Ming Zhang; Yun-Ke Yin; Hai-Bo Hu; Liang-Jie Wang; Jiang Jiang (Environment, Development and Sustainability, 2025)

A new isopimarane-type diterpene with anti-inflammatory activity from the Clinacanthus nutans - Hai-Xia Liao; Can-Can Shi; Rui-Juan Wang; Tai-Ming Shao; Ming-Xiong Tan (Natural Product Research, 2025)

Linking gut microbiome profiles and white matter integrity to social behavior in young autistic children: from the perspective of individual variation - Xinyue Huang; Weixing Zhao; Rui Feng; Yuanyue Zhou; Jia Wang; Jinming Xiao; Lei Li; Xiaolong Shan; Yu Feng; Yating Ming; Jing Cao; Xiaodong Kang; et al. (Science Bulletin, 2025)

Tenecteplase Plus Butyphthalide for Stroke Within 4.5–6 Hours of Onset (EXIT-BT): a Phase 2 Study - Hui-Sheng Chen; Ming-Rui Chen; Yu Cui; Xin-Yu Shen; Hong Zhang; Jiang Lu; Li-Wei Zhao; Ying-Jie Duan; Jing Li; Ya-Mei Wang; Lian-Qiu Min; Li-Hong Zhao; et al. (Translational Stroke Research, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

CORBES: Radiation belt survey with international small satellite constellation - Ji Wu; Li Deng; Jaan Praks; Marius Anger; Philipp Oleynik; Wojciech Hajdas; Jin-Dong Wang; Shen-Yi Zhang; Bin Zhou; Li Zeng; Jinbin Cao; David Fischer; et al. (Advances in Space Research, 2025)

Predictive maintenance for offshore wind farms with incomplete and biased prognostic information - Rui He; Zhigang Tian; Yifei Wang; Yinuo Chen; Ming J. Zuo (Ocean Engineering, 2025)

Molecular identification of three cytochrome P450 genes and their potential roles in insecticides tolerance in Grapholita molesta (Busck) - Hui Han; Ming-Gao Li; Kai-Yang Xing; Qi Wang; Jun Hu; Zhi-Guo Zhao; Qin Yu; Rui-Yan Ma; Ling-Ling Gao; Yan-Qiong Guo (Pesticide Biochemistry and Physiology, 2025)

Aeration strategies for microalgae in wastewater treatment: Enhancing pollutant removal and community dynamics - Pan Li; Yajun Luo; Fei Ming; Jingxian Zheng; Zhicheng Pan; Rui Wang; Yanqing He; Miao Zhou; Xin Xiong; Chi Zhang; Yu Lei; Zhaoqi Wang; et al. (Journal of Environmental Management, 2025)

Environmentally relevant concentrations of DBDPE (decabromodiphenyl ethane) induce intestinal toxicity in silkworms (Bombyx mori L.) - Xue Luo; Rui Xing; Man Xu; Hui-Jun Jiang; Yu-Rui Wang; Ming-Yue Hu; Hao Zhang; Feng Ge; Wei Zhang; Hong-Wei Wang (Environmental Pollution, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Highly selective ppb-level Cl2 sensor at room temperature based on ZIF-8 coated MIL-68(In)-derived hexagonal tubes - Sumin Wang; Rui Gao; Ming Zheng; Xianfa Zhang; Xiaoli Cheng; Yingming Xu; Shan Gao; Xin Zhou; Lihua Huo (Chemical Engineering Journal, 2025)

Isolation and detection strategies for decoding the heterogeneity of extracellular vesicles - Shi-Ming Wang; Dan Wang; Yu-Qing Shen; Mo-Han Wang; Fei Jia; Zhao Pan; Liang Dong; Xian-Yu Zheng; Hui-Qin Wen; Rui Xu (Chemical Engineering Journal, 2025)

Forest Microclimate as a Driver of Epiphytic Bryophyte Diversity Along a Subtropical Elevational Gradient - Zun Dai; Shi‐chen Xing; S. Robbert Gradstein; Min Li; Shu‐wen Tu; Xing Chen; Xue Yao; Shuang Gao; Rui‐ping Shi; Lu‐yan Tang; Ran Zhang; Zhao‐chen Zhang; et al. (Journal of Biogeography, 2025)
Aim Considering the importance of microclimate in maintaining the diversity of epiphytic bryophytes, we investigated epiphytic bryophytes along an elevational gradient in the subtropical forest of eastern China to unravel the diversity patterns of epiphytic liverworts and mosses along the elevational gradients and the roles of forest microclimates, topographic variables and host plant composition attributes in shaping these elevational diversity patterns. Location Tianmushan National Nature Reserve, Zhejiang, China. Taxon Epiphytic bryophytes. Methods Species diversity patterns of liverworts and mosses were compared based on an inventory of 16 plots along an elevational gradient from 367 to 1470 m. In situ microclimatic data of air temperature and moisture were collected under constant monitoring for over 3 years. Spatial linear models and structural equation models were used to assess the relative roles of the environmental variables in shaping the patterns of species diversity along elevation. Results We found that epiphytic liverwort and moss richness showed different elevational patterns; overall richness patterns of epiphytic bryophytes were largely driven by mosses. Epiphytic mosses exhibited a decline, followed by a hump‐shaped pattern of species richness with increasing elevation, while epiphytic liverworts showed a mid‐elevation plateau with a richness maximum between 800 and 1300 m. Forest microclimate, topography and host plant composition attributes influence epiphytic moss and liverwort patterns differently and interact in a complex way. Overall, species richness of epiphytic liverworts was most strongly affected by microclimate (mean annual air temperature of growing season) and of epiphytic mosses richness by topography (slope). Further, epiphytic liverwort species richness was more influenced by temperature than moisture. Main Conclusions This study highlights the importance of collecting climatic factors at a fine scale (microhabitats) for understanding the patterns and drivers of bryophyte diversity. Further, our findings demonstrate the differences between liverworts and mosses in terms of their response to different environments in the forest ecosystem.

Estradiol Enhances Cerebellar Molecular Layer Interneuron-Purkinje Cell Synaptic Transmission and Improves Motor Learning Through ER-β in Vivo in Mice - Yong-Rui Piao; Mei-Rui Li; Ming-Ze Sun; Yang Liu; Chao-Yue Chen; Chun-Ping Chu; Yuki Todo; Zheng Tang; Chun-Yan Wang; Wen-Zhe Jin; De-Lai Qiu (The Cerebellum, 2025)

Regulation roles of dre-miR-187 in neurological damage by low concentration toluene in zebrafish - Shu-Hui Men; Jia-Yun Xu; Zhen-Guang Yan; Jin-Zhe Du; Ming-Rui Li; Zi-Ye Wang; Chen Liu; Xin Zheng (Journal of Cleaner Production, 2025)

Analytical solutions of two-liner tunnels constructed in time-dependent plastic rocks considering loading-unloading stress paths - Hua-ning Wang; Qian Liu; Fei Song; Rui-cong Fu; Ming-jing Jiang (International Journal of Rock Mechanics and Mining Sciences, 2025)

Erroneous Differentiation of Tendon Stem/Progenitor Cells in the Pathogenesis of Tendinopathy: Current Evidence and Future Perspectives - Yucheng Gao; Hao Wang; Liu Shi; Panpan Lu; Guangchun Dai; Ming Zhang; Bowen Han; Mumin Cao; Yingjuan Li; Yunfeng Rui (Stem Cell Reviews and Reports, 2025)

TDCPP promotes apoptosis and inhibits the calcium signaling pathway in human neural stem cells - Ming-Rui Li; Guo-Rui Zhou; Zi-Ye Wang; Bo-Yang Li; Shu-Hui Men; Zhen-Guang Yan (Science of The Total Environment, 2025)

Organic matter accumulation driven by land-sea interactions during the Late Cretaceous: A geochemical study of the Nenjiang Formation, Songliao Basin - Congsheng Bian; Shiju Liu; Wei Liu; Xiong Cheng; Xin Liu; Jin Dong; Rui Wang; Yongxin Li; Ming Guan; Qianhui Tian; Wenzhi Zhao (Organic Geochemistry, 2025)

A multirisk-rescued biomimetic nanozyme against periodontitis via inflammation targeting and microenvironment reprogramming - Lin Li; Rui-Xin Wu; Jia Wang; Rui Jin; Xin-Yu Zhang; Mei Xu; Si-Yao Li; Rui Gao; Bei-Min Tian; Xiao-Tao He; Fa-Ming Chen; Yuan Yin (Chemical Engineering Journal, 2025)

Enhanced wastewater treatment using biochar-supported layered-double-hydroxide composites - Ao Huang; Nan Zhang; Qian-Bin Wang; Bo-Han Zhao; Rui-Bao Zhang; Ming Cheng; Chen Shi; Xiao-Di Hao (Chemical Engineering Journal, 2025)

Enhancing direct air carbon capture into microalgae: A membrane sparger design with carbonic anhydrase integration - Rui-Long Wang; Ming-Jia Li; Gregory J.O. Martin; Sandra E. Kentish (Algal Research, 2025)

Roseobacter weihaiensis sp. nov., a cellulose-degrading bacterium isolated from intestinal content of Nipponacmea schrenckii collected from golden beach in Weihai, China - Yu-Rui Li; Ming-Jing Zhang; Yan-Jun Yi; Xiao-Chen Wang; Dong-Mei San; Yan-Xia Zhou (Antonie van Leeuwenhoek, 2025)

Associations between volatile organic compounds exposure and multiple oxidative damage biomarkers: Method development, human exposure, and application for e-waste pollution prediction - Jia-Rong Wang; Hong-Xuan Kuang; Ye Liu; Xin-Yi Li; Tian-Hong Chen; Xiao-Hui Zhu; Rui-Fang Fan; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

AHR activation relieves deoxynivalenol-induced disruption of porcine intestinal epithelial barrier functions - Zi-Yan Hu; Shang-Jia Yang; Yuan-Hang Chang; Xue-Qi Wang; Rui-Qi Liu; Fu-Wei Jiang; Ming-Shan Chen; Jia-Xin Wang; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Yi Zhao; et al. (Journal of Hazardous Materials, 2024)

Construction mechanisms, synthesis strategies, and photocatalytic applications of homojunction catalysts: A review - Hao-wen Zhu; Rui-tang Guo; Qing-shan Wang; Cong Liu; Heng-fei Cui; Ming-yang Liu; Wei-guo Pan (Journal of Environmental Chemical Engineering, 2024)

Ultrasensitive detection of contaminants in milk using a novel NMS-Ag modified water-resistant paper substrate - Rui Su; Siqi Li; Yugang Su; Zhong Wang; Ming Gao (Food Chemistry, 2024)

Green fabrication of modified lignin/zeolite/chitosan-based composite membranes for preservation of perishable foods - Zhan-Chao Li; Meng-Yao Su; Xiao-Yu Yuan; Hai-Qing Lv; Rui Feng; Li-Jie Wu; Xiao-Ping Gao; Yan-Xia An; Zhan-Wei Li; Miao-Yun Li; Gai-Ming Zhao; Xiao-Peng Wang (Food Chemistry, 2024)

Corrigendum to “A critical review on graphene oxide membrane for industrial wastewater treatment” [Environ. Res. 223 (2023) 115409] - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2024)

Unraveling the chloride ion capture capability of nitrogen-doped porous carbon for capacitive deionization and desalination battery - Huazeng Yang; Rui Zhang; Zhiyuan Liu; Xin Xu; Yishuo Teng; Ming Hou; Guangshuai Zhang; Yongzhao Hou; Guangwu Wen; Dong Wang (Chemical Engineering Journal, 2024)

PABPN1 functions as a predictive biomarker in colorectal carcinoma - Qing-hua Wang; Pei-ci Yan; Li-zhou Shi; Ya-jie Teng; Xiao-jiao Gao; Li-qian Yao; Zhi-wei Liang; Ming-hui Zhou; Wei Han; Rui Li (Molecular Biology Reports, 2024)

Lymph nodes in oral squamous cell carcinoma: a comprehensive anatomical perspective - Guang-Rui Wang; Nian-Nian Zhong; Lei-Ming Cao; Xuan-Hao Liu; Zi-Zhan Li; Yao Xiao; Kan Zhou; Yi-Fu Yu; Bing Liu; Lin-Lin Bu (Clinical & Experimental Metastasis, 2024)

Z-Ligustilide restricts rabies virus replication by inducing ferroptosis through the ACSL4-LPCAT3-POR pathway - Jianqing Zhao; Qianruo Wang; Zhenkun Liu; Meixin Sun; Rui Zhou; Zhen F. Fu; Ling Zhao; Ming Zhou (Veterinary Microbiology, 2024)

Myosuppressin signaling deficiency affects ovarian development via repression of 20-hydroxyecdysone biosynthesis in Grapholita molesta - Jie Cheng; Jing-Kai Liu; Tian-Li Wang; Wei Wei; Hui-Ming Xiang; Xian-Wei Li; Rui-Yan Ma; Zhi-Guo Zhao (Pesticide Biochemistry and Physiology, 2024)

NUS1 Variants Cause Lennox-Gastaut Syndrome Related to Unfolded Protein Reaction Activation - Nan-Xiang Shen; Xiao-Chong Qu; Jing Yu; Cui-Xia Fan; Fu-Li Min; Ling-Ying Li; Ming-Rui Zhang; Bing-Mei Li; Jie Wang; Na He; Wei-Ping Liao; Yi-Wu Shi; et al. (Molecular Neurobiology, 2024)

A Cysteinyl-tRNA Synthetase Mutation Causes Novel Autosomal-Dominant Inheritance of a Parkinsonism/Spinocerebellar-Ataxia Complex - Han-Kui Liu; Hong-Lin Hao; Hui You; Feng Feng; Xiu-Hong Qi; Xiao-Yan Huang; Bo Hou; Chang-Geng Tian; Han Wang; Huan-Ming Yang; Jian Wang; Rui Wu; et al. (Neuroscience Bulletin, 2024)
This study aimed to identify possible pathogenic genes in a 90-member family with a rare combination of multiple neurodegenerative disease phenotypes, which has not been depicted by the known neurodegenerative disease. We performed physical and neurological examinations with International Rating Scales to assess signs of ataxia, Parkinsonism, and cognitive function, as well as brain magnetic resonance imaging scans with seven sequences. We searched for co-segregations of abnormal repeat-expansion loci, pathogenic variants in known spinocerebellar ataxia-related genes, and novel rare mutations via whole-genome sequencing and linkage analysis. A rare co-segregating missense mutation in the CARS gene was validated by Sanger sequencing and the aminoacylation activity of mutant CARS was measured by spectrophotometric assay. This pedigree presented novel late-onset core characteristics including cerebellar ataxia, Parkinsonism, and pyramidal signs in all nine affected members. Brain magnetic resonance imaging showed cerebellar/pons atrophy, pontine-midline linear hyperintensity, decreased rCBF in the bilateral basal ganglia and cerebellar dentate nucleus, and hypo-intensities of the cerebellar dentate nuclei, basal ganglia, mesencephalic red nuclei, and substantia nigra, all of which suggested neurodegeneration. Whole-genome sequencing identified a novel pathogenic heterozygous mutation (E795V) in the CARS gene, meanwhile, exhibited none of the known repeat-expansions or point mutations in pathogenic genes. Remarkably, this CARS mutation causes a 20% decrease in aminoacylation activity to charge tRNA Cys with L-cysteine in protein synthesis compared with that of the wild type. All family members carrying a heterozygous mutation CARS (E795V) had the same clinical manifestations and neuropathological changes of Parkinsonism and spinocerebellar-ataxia. These findings identify novel pathogenesis of Parkinsonism-spinocerebellar ataxia and provide insights into its genetic architecture.

High-altitude exposure leads to increased modularity of brain functional network with the increased occupation of attention resources in early processing of visual working memory - Jing Zhou; Nian-Nian Wang; Xiao-Yan Huang; Rui Su; Hao Li; Hai-Lin Ma; Ming Liu; De-Long Zhang (Cognitive Neurodynamics, 2024)

Association of prenatal multiple metal exposures with child neurodevelopment at 3 years of age: A prospective birth cohort study - Yun Qiu; Yuxin Liu; Ming Gan; Weiting Wang; Tao Jiang; Yangqian Jiang; Hong Lv; Qun Lu; Rui Qin; Shiyao Tao; Lei Huang; Xin Xu; et al. (Science of The Total Environment, 2024)

Jianpi Huayu Prescription Prevents Atherosclerosis by Improving Inflammation and Reshaping the Intestinal Microbiota in ApoE−/− Mice - Hao-Ran Zhao; Qin-Chi Xian; Xuan-Ming Zhang; Xiao-Yu Ma; Fu-Qiao Wang; Rui-Si Wang; Zhi-Jie Liu; Zhi-Gang Zhang (Cell Biochemistry and Biophysics, 2024)
This study established an LPS-induced RAW264.7 macrophage inflammatory injury model and an AS mouse vulnerable plaque model to observe the effect of JPHYP on macrophage inflammation, plaque formation, blood lipids, inflammation levels, intestinal flora and the influence of TLR4/MyD88/MAPK pathway, and explore the anti-AS effect and molecular mechanism of JPHYP, and detected 16S rRNA of mice intestinal microbes. The difference of intestinal flora in different groups of mice was compared to further explore the intervention effect of JPHYP and clarify the molecular biological mechanism of JPHYP in preventing and treating AS by regulating TLR4/MyD88/MAPK inflammatory signaling pathway and improving intestinal flora.

In vivo manufacture and manipulation of CAR-T cells for better druggability - Rui Hou; Xiaoxue Zhang; Xu Wang; Xuan Zhao; Sijin Li; Zhangchun Guan; Jiang Cao; Dan Liu; Junnian Zheng; Ming Shi (Cancer and Metastasis Reviews, 2024)

Heterologous expression and characterization of two delta glutathione S-transferases genes involved in imidacloprid metabolism in Grapholita molesta - Qin-Wei Pang; Wen-Jie He; Ming-Gao Li; Ming Wang; Xue-Yao Zhang; Li-Jun Zhang; Ling-Ling Gao; Rui-Yan Ma; Yan-Qiong Guo; Qin Yu (Chemosphere, 2024)

The mitigation of citric acid on cadmium toxicity in Iris tectorum and its effects on the composition of cell walls - Xiao-Fang Yu; Zhi-Wen Wang; Feng-Lian Chen; Mao-Lin Chen; Xin-Yu Zhang; Jun-Rui Zhang; Wen-Yu Ji; Xue Xiao; Li-Juan Yang; Ting Lei; Xi Li; Ming-Yan Jiang (International Biodeterioration & Biodegradation, 2024)

Mantle-rooted fluid pathways and world-class gold mineralization in the giant Jiaodong gold province: Insights from integrated deep seismic reflection and tectonics - Li-Qiang Yang; Jun Deng; Liang Zhang; Ai-Hua Zhao; M. Santosh; Xue-Feng Yu; Wei Yang; Da-Peng Li; Wei Shan; Dong Xie; Xiang-Dong Liu; Xue Gao; et al. (Earth-Science Reviews, 2024)

Gradient lithiophilic structure for the homogenized electric field strength to achieve dendrite-free lithium metal anode - Yan Dong; Rui Wang; Jianhua Wang; Zhenshan Yang; Longfei Li; Qianhui Wu; Lubin Ni; Guowang Diao; Ming Chen (Chemical Engineering Journal, 2024)

Mechanism of phenols evolution during pyrolysis of Shendong coal macerals swelled with oxygen-containing organic solvents: Experimental and DFT study - Linyang Wang; Qiuxiang Yao; Rui Cao; Lei He; Ming Sun; Xiaoxun Ma (Chemical Engineering Journal, 2024)

An “off-on-enhanced on” electrochemiluminescence biosensor based on resonance energy transfer and surface plasmon coupled 3D DNA walker for ultra-sensitive detection of microRNA-21 - Meng-Li Li; Ming-Yu Zhong; Jia Zhang; Yi-Jia Zhang; Yu-Qi Zhang; Yan Liu; Xiang-Kai Li; Shu-Tian Gan; Gong-Rui Meng; Li Mi; Yong-Hong Hu; Fang Zhang; et al. (Analytica Chimica Acta, 2024)

Targeting gut microbiota for immunotherapy of diseases - Ya-Jie Yu; Xiao-Dong Liu; Cai Liao; Rui Yu; Xin Wang; Ming Li; Yun Wang (Archives of Toxicology, 2024)

Impact of high-altitude environments on the motion and settling characteristics of wet-mix shotcrete dust in tunnels - Guoliang Zhang; Zhongan Jiang; Xiaocuan Li; Ya Chen; Bin Yang; Mingli Si; Rui Feng; Ming Wang (Tunnelling and Underground Space Technology, 2024)

Comprehensive analysis of metal(loid)s and associated metal(loid) resistance genes in atmospheric particulate matter - Xiu-Peng Liang; He-Jing Wang; Jie-Ru Zheng; Xiao-Ru Wang; Dao-Ming Lin; Ya-Qing Wu; Rui-Lian Yu; Gong-Ren Hu; Yu Yan (Science of The Total Environment, 2024)

Per- and polyfluoroalkyl substances and human health outcomes: An umbrella review of systematic reviews with meta-analyses of observational studies - Wei-Yi Xing; Jia-Nan Sun; Fang-Hua Liu; Li-Shen Shan; Jia-Li Yin; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Jia-Xin Liu; Wen-Rui Zheng; Ying-Ying Zhang; Xin-Jian Song; et al. (Journal of Hazardous Materials, 2024)

Indentification of coal-origin structural units by multi-step pyrolysis through Py-GC/MS and by DFT calculation - Lei He; Qiuxiang Yao; Rui Cao; Linyang Wang; Wei Wang; Duo Ma; Ming Sun; Xiaoxun Ma (Chemical Engineering Journal, 2024)

Attitude inversion of space debris based on the laboratory-tested photometry dataset - Shu-Shu Wang; Hou-Yuan Lin; An-Ming Kang; Jin-Rui Men; Chang-Yin Zhao (Advances in Space Research, 2024)

North Lhasa terrane in the Precambrian originated from Western Australia - Changsheng Yu; Ming Wang; Di Shen; Mengxian Lin; Shengshuo Zhang; Rui Yang; Danzeng Quewang (Precambrian Research, 2024)

Lotus pollen-derived nitrogen and phosphorus self-doped TiO2/carbon materials for photoelectrochemical application - Rui Chen; Ying-Ying Wang; Xia Jiang; Ming-Hao Ji; Ke-Xian Li; Hao-Yan Shi; Hai-Long Wang; Yan-Xin Chen; Can-Zhong Lu (Journal of Environmental Chemical Engineering, 2024)

A randomised double-blind placebo-controlled trial of a probiotic combination for manipulating the gut microbiota and managing metabolic syndrome - Rui Xiao; Ying Chen; Xiaofeng Zhu; Linlin Wang; Peijun Tian; Xing Jin; Ming Liang; Zehua Chen; Ting Zhang; Long Qian; Qun Wang; Jianxin Zhao; et al. (Food Bioscience, 2024)

Experimental Study on the Hot Surface Ignition Characteristics and a Predictive Model of Marine Diesel in a Ship Engine Room - Kan Wang; Rui Qiu; Yang Ming; Hang Xu (Journal of Marine Science and Engineering, 2024)
To ensure the safe protection of marine engine systems, it is necessary to explore the hot surface ignition (HSI) characteristics of marine diesel in ship environments. However, an accurate model describing these complex characteristics is still not available. In this work, a new experimental method is proposed in order to enhance prediction performance by integrating testing data of the characteristics of HSI of marine diesel. The sensitivity of HSI is determined by various factors such as surface parameters, flow state, and the ship’s environment. According to variations in the HSI status of marine diesel in an engine room, the HSI probability is distributed in three phases. It is essential to determine whether the presence of marine diesel or surrounding items can intensify the risk of an initial fire beginning in the engine room. A vapor plume model was developed to describe the relationship between HSI height and initial specific buoyancy flux in vertical space. Further, field distribution revealed significant variation in the increase in temperature between 200 and 300 mm of vertical height, indicating a region of initial HSI. In addition, increasing surface temperature did not result in a significant change in ignition delay time. After reaching a temperature of 773 K, the ignition delay time remained around 0.48 s, regardless of how much the hot surface temperature increased. This study reveals the HSI evolution of marine diesel in a ship engine room and develops data-based predictive models for evaluating the safety of HSI parameters during initial accident assessments. The results show that the goodness of fit of the predictive models reached above 0.964. On the basis of the predicted results, the HSI characteristics of marine diesel in engine rooms could be gleaned by actively determining the parameters of risk.

Weakened hydrological oscillation period increased the frequency of river algal blooms - Qiang HU; Yan CHEN; Rui XIA; Xiaoyu LIU; Ruining JIA; Kai ZHANG; Xiaoxuan LI; Chao YAN; Yao WANG; Yingze YIN; Xiang LI; Junde MING (Water Research, 2024)

Role and action mechanisms of miR-149 and miR-31 in regulating function of pig cumulus cells and oocytes - Jia-Shun Wu; Shuai Gong; Min Zhang; Rui-Jie Ma; Hui-Li Wang; Ming-Jiu Luo; Nan He; Jing-He Tan (Theriogenology, 2024)

Biotemplated fabrication of N/O co-doped porous carbon confined spinel NiFe2O4 heterostructured mimetics for triple-mode sensing of antioxidants and ameliorating packaging properties - Yuan Gao; Juan Wang; Lin-Lan Zhao; Bo-Yi Yuan; Ya-Nan Kong; Jing-Jing Luo; Shu-Chang Zhao; Wei-Ming Yang; Rui-Lin Liu (Food Chemistry, 2024)

Curvularin derivatives from the marine mangrove derived fungus Penicillium sumatrense MA-325 - Yi-Ran Wang; Yu-Liang Dong; Xiao-Ming Li; Xiao-Shan Shi; Hong-Lei Li; Ling-Hong Meng; Rui Xu; Bin-Gui Wang (Phytochemistry, 2024)

Non-fitting functional representation for the equilibrium constant subject to reaction between H2S and CO2 - Chao-Wen Wang; Ji Li; Lie-Hui Zhang; Qun-Chao Ding; Guan-Hong Liu; Gao Li; Rui Jiang; Xiao-Long Peng; Lin-Sheng Wei; Hong-Ming Tang; Jian-Yi Liu; Chun-Sheng Jia (Fuel, 2024)

Controlled assembly of novel Fe2O3/MgFe2O4 nanotubular array structures for rapid detection of dibutylamine - Baosheng Li; Junchao Yang; Guanyi Zhang; Ming Zheng; Rui Li; Yubao Kan; Jiahui Li; Tingting Wang; Qibin Huang; Xianfa Zhang; Lihua Huo; Shan Gao; et al. (Chemical Engineering Journal, 2024)

Andesitic arc magmas derived from two contrasting mélange origins: Evidence from central Tibetan dioritic porphyries - Lu-Lu Hao; Qiang Wang; Andrew C. Kerr; Fang Huang; Ming Xiao; Xiao-Long Ma; Wan-Feng Zhang; Wen-Yu Wang; Mao-Rui Liu (Chemical Geology, 2024)

The Complete Genomic Sequence of Microbial Transglutaminase Producer, Streptomyces mobaraensis DSM40587 - Xi-long Feng; Rui-qi Zhang; Wei-ge Dong; Zhen-xin Wang; Jun-jie Xiao; Jing Wei; Jin-ming Gao; Jianzhao Qi (Biochemical Genetics, 2024)

Topological spin-orbit-coupled fermions beyond rotating wave approximation - Han Zhang; Wen-Wei Wang; Chang Qiao; Long Zhang; Ming-Cheng Liang; Rui Wu; Xu-Jie Wang; Xiong-Jun Liu; Xibo Zhang (Science Bulletin, 2024)

Sesquiterpenoid derivatives isolated from a liquid culture of Hypholoma capnoides 819 - Yu-Ting Wang; Hong-Yu Tan; Xue Zhao; Yu Yang; Rui Xu; Shuai-Ming Zhu; Hao Ma; Fu-Yao Luo; Cai-Hong Dong; Chang-Wei Li (Phytochemistry, 2024)

De-branching of starch molecules enhanced the complexation with chitosan and its potential utilization for delivering hydrophobic compounds - Min Liu; Min Zhuang; Dengdeng Li; Jinxu Fan; Rui Wang; Xuanyu Wang; Sheng Ke; Ming Ning; Zhongkai Zhou (Food Hydrocolloids, 2024)

Dynamic spillover effects between EU economic sanctions against Russia, oil prices, and share prices of energy companies in third countries: evidence from China and the USA - Ming Li; Zaixu Zhang; Xiaoyu Wang; Rui Guo (Environmental Science and Pollution Research, 2024)

Co-application of concentrated biogas slurry and pyroligneous liquor mitigates ammonia emission and sustainably releases ammonium from paddy soil - Zichuan Li; Rui Zhang; Jianfeng Jiang; Yanjun Chai; Haijun Yang; Yutong Zong; Wenbin Tong; Mengting Yuan; Ronghui Li; Lanting Wang; Shengdao Shan; Ming Hung Wong (Science of The Total Environment, 2024)

The application of human-derived cell lines in neurotoxicity studies of environmental pollutants - Ming-Rui Li; Shu-Hui Men; Zi-Ye Wang; Chen Liu; Guo-Rui Zhou; Zhen-Guang Yan (Science of The Total Environment, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

Salvirrane A-F, six undescribed nordrimane sesquiterpene derivatives from Salvia castanea Diels f. tomentosa Stib and their cytotoxic activities - Rui Zhang; Dong-Dong Wang; Lian-Yu Tang; Peng-Xue Ji; Xin-Min Li; Zi-Feng Guo; Jue Wang; Jing-Ming Jia; An-Hua Wang (Phytochemistry, 2024)

Aridity drives the variability of desert soil microbiomes across north-western China - Lei Dong; Mei-Xiang Li; Shuai Li; Ling-Xiang Yue; Mukhtiar Ali; Jia-Rui Han; Wen-Hui Lian; Chao-Jian Hu; Zhi-Liang Lin; Guo-Yuan Shi; Pan-Deng Wang; Shao-Ming Gao; et al. (Science of The Total Environment, 2024)

Human activity and climate change accelerate the extinction risk to non‐human primates in China - Wen‐Bo Li; Yang Teng; Ming‐Yi Zhang; Ying Shen; Jia‐Wen Liu; Ji‐Wei Qi; Xiao‐Chen Wang; Rui‐Feng Wu; Jin‐Hua Li; Paul A. Garber; Ming Li (Global Change Biology, 2024)
Human activity and climate change affect biodiversity and cause species range shifts, contractions, and expansions. Globally, human activities and climate change have emerged as persistent threats to biodiversity, leading to approximately 68% of the ~522 primate species being threatened with extinction. Here, we used habitat suitability models and integrated data on human population density, gross domestic product (GDP), road construction, the normalized difference vegetation index (NDVI), the location of protected areas (PAs), and climate change to predict potential changes in the distributional range and richness of 26 China's primate species. Our results indicate that both PAs and NDVI have a positive impact on primate distributions. With increasing anthropogenic pressure, species' ranges were restricted to areas of high vegetation cover and in PAs surrounded by buffer zones of 2.7–4.5 km and a core area of PAs at least 0.1–0.5 km from the closest edge of the PA. Areas with a GDP below the Chinese national average of 100,000 yuan were found to be ecologically vulnerable, and this had a negative impact on primate distributions. Changes in temperature and precipitation were also significant contributors to a reduction in the range of primate species. Under the expected influence of climate change over the next 30–50 years, we found that highly suitable habitat for primates will continue to decrease and species will be restricted to smaller and more peripheral parts of their current range. Areas of high primate diversity are expected to lose from 3 to 7 species. We recommend that immediate action be taken, including expanding China's National Park Program, the Ecological Conservation Redline Program, and the Natural Forest Protection Program, along with a stronger national policy promoting alternative/sustainable livelihoods for people in the local communities adjacent to primate ranges, to offset the detrimental effects of anthropogenic activities and climate change on primate survivorship.

The co-regulation of the gut microbiome and host genes might play essential roles in metformin gastrointestinal intolerance - Huixiang Zhang; Jiao Lai; Lihuan Zhang; Wei Zhang; Xun Liu; Qilin Gong; Hongxi Tian; Mingzhi Yang; Tao Yang; Rui Zhao; Dongqing Li; Hehua Huang; et al. (Toxicology and Applied Pharmacology, 2023)

Seroprevalence and potential risk factors of brucellosis in sheep from America, Africa and Asia regions: A systematic review and meta-analysis - Lian-Min Li; Qi Wang; Jun-Feng Shi; Ting Li; Bo Zhao; Qing-Xia Ma; Hong-Ying Liu; Nuo Su; Ruo-Peng Cai; Fan-Li Zeng; Qing-Long Gong; Kun Shi; et al. (Research in Veterinary Science, 2023)

A review of the toxic effects of ammonia on invertebrates in aquatic environments - Tian-Xu Zhang; Ming-Rui Li; Chen Liu; Shu-Ping Wang; Zhen-Guang Yan (Environmental Pollution, 2023)

Epithelial lining inspired protective shield for prolonged endotracheal intubation - Baisong Zhao; Meng-Han Bai; Luxi Zhang; Qingning Wang; Yongying Pan; Yan-Pu Li; Rui Hong; Juxiang Gou; Dongjie Zhang; Yuwei Liu; Gan-Ji Zhong; Ka Li; et al. (Chemical Engineering Journal, 2023)

Demethylation-Driven ligase chain reaction for simultaneously sensitive detection of m6A demethylase FTO and m1A demethylase ALKBH3 in breast cancer at Single-Molecule level - Ming-hao Liu; Qian Zhang; Wan-tong Yu; Jian-Ge Qiu; Hui-min Yuan; Chuan-rui Wang; Bing-Hua Jiang; Yan Zhang; Chun-yang Zhang (Chemical Engineering Journal, 2023)

Induction of Anxiety-Like Phenotypes by Knockdown of Cannabinoid Type-1 Receptors in the Amygdala of Marmosets - Lin Zhu; Di Zheng; Rui Li; Chen-Jie Shen; Ruolan Cai; Chenfei Lyu; Binliang Tang; Hao Sun; Xiaohui Wang; Yu Ding; Bin Xu; Guoqiang Jia; et al. (Neuroscience Bulletin, 2023)

Discrete element-based regression analysis of initial ground stress and application to an extra-long tunnel in China - Ming-Rui Luo; Cheng-You Zhang; Bo Wang; Yan-Hua Zeng (Bulletin of Engineering Geology and the Environment, 2023)

Analysis of spatial and temporal variation of vegetation NPP in Daning River Basin and its driving forces - Wenqian Bai; Li He; Zhengwei He; Xueman Wang; Yang Zhao; Rui Qu; Fang Luo; Xin Chen; Zhifei Wang; Ming Liu (International Journal of Remote Sensing, 2023)

Microplastics affect soil bacterial community assembly more by their shapes rather than the concentrations - Peng-Yang Wang; Ze-Ying Zhao; Xiao-Bin Xiong; Ning Wang; Rui Zhou; Zhi-Ming Zhang; Fan Ding; Meng Hao; Song Wang; Yue Ma; Aimee Grace Uzamurera; Kai-Wen Xiao; et al. (Water Research, 2023)

Effects of interspecific interactions on soil carbon emission and efficiency in the semiarid intercropping systems - Wei Wang; Meng-Ying Li; Rui Zhou; Shuang-Guo Zhu; Hong-Yan Tao; Aziz Khan; Aimee Grace Uzamurera; Bao-Zhong Wang; Jun-Ming Jin; Yue Ma; Wen-Bo Li; Xiu-Ping Tao; et al. (Soil and Tillage Research, 2023)

Anti-inflammatory metabolites from the fruits of Pittosporum elevaticostatum - Jun-Rui Ren; Xin-Zheng Liu; Wei-Zhen Kong; Zhao-Xuan Wang; Jin-Ming Gao; Xiu-Yun Zhang (Phytochemistry Letters, 2023)

Symbiotic hemolymph bacteria reduce hexavalent chromium to protect the host from chromium toxicity in Procambarus clarkii - Cheng-Ming Yin; Rui-Geng Niu; Hui Wang; Xian-Yao Li; Qi-Fan Zeng; Jiang-Feng Lan (Journal of Hazardous Materials, 2023)

Rapid imaging approach for marine controlled-source electromagnetic with deployed transmission system - Rui Yang; Xuben Wang; Meng Wang; Xianhu Luo; Ming Deng; Jianen Jing; Kai Chen (Journal of Applied Geophysics, 2023)

Damage detection of foundation pile in high-pile wharf based on statistical high-order moment of dynamic response under regular wave excitation - Rui-hu Zhu; Qi-ming Wang; Jin-hai Zheng; Hai-kun Zeng; Jia-bao Zhang; Yan Hu; Cheng-ming Li (Ocean Engineering, 2023)

Controllable micro cross-linking towards multifunctional flame-retardant aliphatic polyamide - Qin Zhang; Guo-Rui Zhu; Xiang-Xin Xiao; Qing-Song Liu; Min Jiang; De-Ming Guo; Hai-Bo Zhao; Wen-Da Li; Li Chen; Bo-Wen Liu; Yu-Zhong Wang (Chemical Engineering Journal, 2023)

Unraveling the role of unpaired 3d electrons in e orbital of CoO: Driving π feedback of N2 for efficient ammonia electrosynthesis - Yuanyuan Xiong; Liang Zhao; Rui Zhao; Xiaoxuan Wang; Xinyue Chi; Kaixin Zhang; Zhenzhen Fu; Shuyuan Li; Jiaou Wang; Kaiqi Nie; Zhiyu Yang; Yi-Ming Yan (Chemical Engineering Journal, 2023)

Structural characteristics of the moss (bryophyte) layer and its underlying soil structure and water retention characteristics - Xia Hu; Zhou Gao; Xiao-Yan Li; Rui-Zhe Wang; Yuan-Ming Wang (Plant and Soil, 2023)

Effect of a novel joint connection of UHPC wet joint and tapered sleeve locking-type couplers on the lateral cyclic response of precast segmental railway bridge columns - Yuxuan Wang; Zhao Cheng; Shuai Li; Jingquan Wang; Rui Zhong; Min Zeng; Fayan Ming; Bing Cui (Engineering Structures, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Different dietary fibers unequally remodel gut microbiota and charge up anti-obesity effects - Jia-Jia Wen; Ming-Zhi Li; Jie-Lun Hu; Jiang Wang; Zhi-Qiang Wang; Chun-Hua Chen; Jing-Rui Yang; Xiao-Jun Huang; Ming-Yong Xie; Shao-Ping Nie (Food Hydrocolloids, 2023)

The Regulation of the AMPK/mTOR Axis Mitigates Tendon Stem/Progenitor Cell Senescence and Delays Tendon Aging - Guangchun Dai; Yingjuan Li; Ming Zhang; Panpan Lu; Yuanwei Zhang; Hao Wang; Liu Shi; Mumin Cao; Renwang Shen; Yunfeng Rui (Stem Cell Reviews and Reports, 2023)

Photo-assisted thermal catalysis for methanol synthesis from methane oxidation on Cu-MOR/g-C3N4 - Yan-Qun Chen; Rui-Xin Zhang; Miao Ren; Ya-Xin Jin; Wen-Jing Wang; Jia-Yao Feng; Zhi-Hua Gao; Zhi-Feng Yan; Yi-Ming Liu; Wei Huang; Lei Liu; Zhi-Jun Zuo (Fuel, 2023)

Manipulating electron redistribution of active sites by in situ engineering B-S-V bond in VS2 catalyst for stable nitrogen fixation - Xinyue Chi; Rui Zhao; Xiaoxuan Wang; Yuanyuan Xiong; Kaixin Zhang; Zhenzhen Fu; Yebo Yao; Shuyuan Li; Zhi-Yu Yang; Yi-Ming Yan (Chemical Engineering Journal, 2023)

Comparative transcriptomes analysis of the ovary reveals potential ovarian development-related genes and pathways in Macrobrachium rosenbergii - Yan-Hao Yang; Rui Wang; Ming Li; Hui-Zan Yang; Guang-Hua Huang; Ke-Yi Ma; Gao-Feng Qiu; Yong Lin (Invertebrate Reproduction & Development, 2023)

Online robustness damage identification of dynamic response of high pile wharf under wave excitation - Yan Hu; Qi-ming Wang; Rui-hu Zhu; Cheng-ming Li; Ning Wang (Ocean Engineering, 2023)

Lignin-based covalent organic polymers with improved crystallinity for non-targeted analysis of chemical hazards in food samples - Zhan-Chao Li; Wei Li; Rui Wang; Dong-Xia Wang; An-Na Tang; Xiao-Peng Wang; Xiao-Ping Gao; Gai-Ming Zhao; De-Ming Kong (Journal of Hazardous Materials, 2023)

A critical review on graphene oxide membrane for industrial wastewater treatment - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2023)

Modulation of the interfacial properties of TiN coatings to generate Rigid-Flexible SEI for better SiO anodes - Hebang Shi; He Zhang; Rui Wang; Ming Liu; Zihan Shen; Jingbo Chen; Binbin Wu; Maoqiao Xiang; Jun Li; Huigang Zhang; Pengpeng Lv; Qingshan Zhu (Chemical Engineering Journal, 2023)

Co-cultivation of microalgae-activated sludge for municipal wastewater treatment: Exploring the performance, microbial co-occurrence patterns, microbiota dynamics and function during the startup stage - Xin Li; Jian Liu; Jiansong Tian; Zhicheng Pan; Yangwu Chen; Fei Ming; Rui Wang; Lin Wang; Houzhen Zhou; Junjie Li; Zhouliang Tan (Bioresource Technology, 2023)

Targeting Senescent Tendon Stem/Progenitor Cells to Prevent or Treat Age-Related Tendon Disorders - Hao Wang; Guang-Chun Dai; Ying-Juan Li; Min-Hao Chen; Pan-Pan Lu; Yuan-Wei Zhang; Ming -Zhang; Mu-Min Cao; Yun-Feng Rui (Stem Cell Reviews and Reports, 2023)

Reduced plastic film mulching under zero tillage boosts water use efficiency and soil health in semiarid rainfed maize field - Ai-Tian Ren; Ji-Yuan Li; Ling Zhao; Rui Zhou; Jian-Sheng Ye; Yi-Bo Wang; Xu-Cheng Zhang; Kiprotich Wesly; Ming-Sheng Ma; You-Cai Xiong (Resources, Conservation and Recycling, 2023)

The circadian regulation of extracellular ATP - Xin Wang; Yu-Ting Dong; Xiu-Ming Hu; Ji-Zhou Zhang; Nan-Rui Shi; Yan-Qin Zuo; Xu Wang (Purinergic Signalling, 2023)
Extracellular ATP is a potent signaling molecule released from various cells throughout the body and is intimately involved in the pathophysiological functions of the nervous system and immune system by activating P2 purinergic receptors. Recent increasingly studies showed that extracellular ATP exhibits circadian oscillation with an approximately 24-h periodicity, which participates in regulatory pathways of central oscillator suprachiasmatic nucleus and peripheral oscillator bladder, respectively. Oscillators modulate the protein expression of ATP release channels and ectonucleotidase activity through clock genes; indeed, real-time alterations of ATP release and degradation determine outcomes of temporal character on extracellular ATP rhythm. The regulatory pathways on extracellular ATP rhythm are different in central and peripheral systems. In this review, we summarize the circadian rhythm of extracellular ATP and discuss several circadian regulatory pathways in different organs via ATP release and degradation, to provide a new understanding for purinergic signaling in the regulatory mechanism of circadian rhythm and a potential target to research the circadian regulation of extracellular ATP in other circadian oscillators.

Spallation damage of underground openings caused by excavation disturbance of adjacent tunnels - Rui Zhao; Ming Tao; Chengqing Wu; Shaofeng Wang; Jianbo Zhu (Tunnelling and Underground Space Technology, 2023)

MiR-130/SNAP-25 axis regulate presynaptic alteration in anterior cingulate cortex involved in lead induced attention deficits - Tao Wang; Rui-Li Guan; Yun-Feng Zou; Gang Zheng; Xue-Feng Shen; Zi-Peng Cao; Rui-Hua Yang; Ming-Chao Liu; Ke-Jun Du; Xue-Hang Li; Michael Aschner; Ming-Gao Zhao; et al. (Journal of Hazardous Materials, 2023)

Longitudinal shear behavior and design method of UHPC connection for prefabricated slabs in composite beams - Hao Wang; Xiao-gang Liu; Qing-rui Yue; Ning Wang; Ming-zhao Zheng (Engineering Structures, 2023)

Different roles of primary and secondary sources in reducing PM2.5: Insights from molecular markers in Pearl River Delta, South China - Kong Yang; Duo-Hong Chen; Xiang Ding; Jun Li; Yu-Qing Zhang; Tao Zhang; Qiao-Yun Wang; Jun-Qi Wang; Qian Cheng; Hao Jiang; Ping Liu; Zi-Rui Wang; et al. (Atmospheric Environment, 2023)

Retraction Note: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2023)

Evaluation of LiNiO2 with minimal cation mixing as a cathode for Li-ion batteries - Rio Akbar Yuwono; Fu-Ming Wang; Nae-Lih Wu; Yan-Cheng Chen; Hsi Chen; Jin-Ming Chen; Shu-Chih Haw; Jyh-Fu Lee; Rui-Kun Xie; Hwo-Shuenn Sheu; Po-Ya Chang; Chusnul Khotimah; et al. (Chemical Engineering Journal, 2023)

Facile fabrication of hierarchically porous melamine foam@COF composite for sample treatment of non-targeted food safety analysis and oil/water separation - Wei Li; Wei-Liang Jin; Hong-Xin Jiang; Rui Wang; Hao Jia; Jing-Qi Liu; An-Na Tang; Li-Na Zhu; De-Ming Kong (Chemical Engineering Journal, 2023)

Multifunctional lysosome-targetable fluorescent probe for imaging peroxynitrite in acute liver injury model - Kai Wang; Rui Guo; Xu-Yang Chen; Yu-Shun Yang; Lu-Qin Qiao; Ming-Lin Wang (Chemical Engineering Journal, 2023)

Occurrence, correlation, and partitioning of organophosphate esters in soil and tree bark from a megacity, Western China - Can Wang; Rui-Yu Yuan; Shi-Qiang Wei; Ming-Jing He (Environmental Science and Pollution Research, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

Proteomic analysis of coarse and fine skin tissues of Liaoning cashmere goat - Zhixian Bai; Yanan Xu; Ming Gu; Weidong Cai; Yu Zhang; Yuting Qin; Rui Chen; Yinggang Sun; Yanzhi Wu; Zeying Wang (Functional & Integrative Genomics, 2022)

Long non‑coding RNA PART1: dual role in cancer - Rui Ran; Chao-Yang Gong; Zhi-Qiang Wang; Wen-Ming Zhou; Shun-Bai Zhang; Yong-Qiang Shi; Chun-Wei Ma; Hai-Hong Zhang (Human Cell, 2022)

Spatial-temporal distribution and tectonic setting of Mesozoic W-mineralized granitoids in the Xing-Meng Orogenic Belt, NE China - Wei Xie; Qing-Dong Zeng; Rui-Liang Wang; Jin-Jian Wu; Zhe-Ming Zhang; Feng-Chun Li; Zhuang Zhang (International Geology Review, 2022)

RIG-I acts as a tumor suppressor in melanoma via regulating the activation of the MKK/p38MAPK signaling pathway - Rui Guo; Shun-Yuan Lu; Jin-Xia Ma; Qian-Lan Wang; Lu Zhang; Ling-Yun Tang; Yan Shen; Chun-Ling Shen; Jin-Jin Wang; Li-Ming Lu; Zhu-Gang Wang; Hong-Xin Zhang (Human Cell, 2022)
Studies have indicated that RIG-I may act as a tumor suppressor and participate in the tumorigenesis of some malignant diseases. However, RIG-I induces distinct cellular responses via different downstream signaling pathways depending on the cell type. To investigate the biological function and underlying molecular mechanism of RIG-I in the tumorigenesis of melanoma, we constructed RIG-I knockout, RIG-I -overexpressing B16-F10 and RIG-I knockdown A375 melanoma cell lines, and analyzed the RIG-I-mediated change in the biological behavior of tumor cells in spontaneous and poly (I:C)-induced RIG-I activation. Cell proliferation, cell cycling, apoptosis and migration were detected by CCK-8 assay, BrdU incorporation assay, Annexin V–PI staining assay and Transwell assay, respectively. In vivo tumorigenicity was evaluated by tumor xenograft growth in nude mice and subsequently by Ki67 staining and TUNEL assays. Furthermore, Western blotting was utilized to explore the underlying mechanism of RIG-I in melanoma cells. Our data showed that RIG-I promotes apoptosis and inhibits proliferation by G1 phase cell cycle arrest in the melanoma cell lines. Mechanistically, RIG-I induced the phosphorylation of p38 MAPK and MAPK kinases MKK3 and MKK4. In conclusion, the current study demonstrated that RIG-I suppressed the development of melanoma by regulating the activity of the MKK/p38 MAPK signaling pathway, which is relevant to research on novel therapeutic targets for this malignant disease.

Reduction the contamination of patulin during the brewing of apple cider and its characteristics - Zhouli Wang; Leran Wang; Qiaoying Ming; Tianli Yue; Qian Ge; Yahong Yuan; Zhenpeng Gao; Rui Cai (Food Additives & Contaminants: Part A, 2022)

Identification of the Largest SCA36 Pedigree in Asia: with Multimodel Neuroimaging Evaluation for the First Time - Yue Xie; Zhao Chen; Zhe Long; Rui-Ting Chen; Yi-Zheng Jiang; Ming-Jie Liu; Lin-Liu Peng; Hui-Rong Peng; Na Wan; Guangdong Zou; Chun-Rong Wang; Yu-Ting Shi; et al. (The Cerebellum, 2022)

Transcriptomic Analysis of Circulating Neutrophils in Sheep with Mineral Element Imbalance - Di Wang; Ming Ji; Qijun Zhou; Chengyuan Su; Shuai Lian; Jianfa Wang; Jiasan Zheng; Rui Wu (Biological Trace Element Research, 2022)

Focal white matter microstructural alteration after anthracycline-based systemic treatment in long-term breast cancer survivors: a structural magnetic resonance imaging study - Huawen Zhang; Peng Li; Tonghui Liu; Xueyuan Wang; Wei Feng; Rui Chen; Hengyang Wei; Guoqiang Li; Long Ning; Ming Zhang; Yuchen Zhang (Brain Imaging and Behavior, 2022)

Oxygen Metabolism-induced Stress Response Underlies Heart–brain Interaction Governing Human Consciousness-breaking and Attention - Xiao-Juan Xue; Rui Su; Ze-Feng Li; Xiao-Ou Bu; Peng Dang; Si-Fang Yu; Zhi-Xin Wang; Dong-Mei Chen; Tong-Ao Zeng; Ming Liu; Hai-Lin Ma; De-Long Zhang (Neuroscience Bulletin, 2022)

Surface wind and vertical extent features of the explosive cyclones in the Northern Hemisphere based on the ERA‐I reanalysis data - Li‐Zhi Jiang; Shen‐Ming Fu; Jian‐Hua Sun; Rui Fu; Wan‐Li Li; Si‐Xiong Zhao; Hui Wang (International Journal of Climatology, 2022)
Although explosive cyclones (ECs) have long been a focus of research, there remains a lack of knowledge of the statistical characteristics of their associated maximum surface winds and vertical extents. This study fills this gap by conducting a targeted statistical analysis of ECs in the Northern Hemisphere using the ERA‐I reanalysis data during a 40‐year period. Some new findings are obtained: (a) The average location of formation of ECs undergoes a notable westward and equatorward shift from September to April in the next year which is consistent with the location variations of sea surface temperature's strong gradients in subtropical regions. (b) Extreme ECs with a deepening rate more than 2.0 Bergeron or with a longer lifespan more than 10 days tend to have a larger occurrence number over the Northern Atlantic Ocean than over the Northern Pacific. (c) The maximum surface wind associated with an EC tends to appear between the EC reaching its maximum deepening rate and reaching its minimum central pressure. (d) The northeastern quadrant of ECs accounts for the highest proportion of maximum surface wind and strongest wind speed, as the baroclinic energy conversion is generally strongest in this quadrant. (e) Over 60% of ECs belong to a type of vertically deep cyclone (ECs' top levels show close relationship to ascending motions within their central regions), and they tend to reach their maximum vertical extent around the time when they reach their minimum central pressures. (f) The highest top levels of ECs exhibit an overall upward extending trend as their minimum central pressure decreases or their maximum deepening rate increases.

Triculata A, a novel compound from Tricyrtis maculata (D. Don) J. F. Macbr. with biological properties - Li Ren; Yun-Ze Wang; Wei Zhang; Rui Zhou; Ming Zhao; Zhi-Shu Tang; Jing Sun; Dong-Bo Zhang (Natural Product Research, 2021)

Loganin ameliorates depression-like behaviors of mice via modulation of serotoninergic system - Chen-Hao Pan; Cong-Yuan Xia; Yu Yan; Yan Han; Rui Shi; Jun He; Ze-Xing Wang; Yu-Ming Wang; Wei-Ku Zhang; Jie-Kun Xu (Psychopharmacology, 2021)

Effects of organic acids on the chemotaxis profiles and biocontrol traits of antagonistic bacterial endophytes against root-rot disease in Panax notoginseng - Li Ma; Wu-Qin Wang; Rui Shi; Xue-Mei Zhang; Xin Li; Yu-Sen Yang; Ming He Mo (Antonie van Leeuwenhoek, 2021)

Microseismic source location method based on a velocity model database and statistical analysis - Bing-Rui Chen; Tao Li; Xin-Hao Zhu; Fan-Bo Wei; Xu Wang; Ming-Xing Xie (Arabian Journal of Geosciences, 2021)

Insights into heat response mechanisms in Clematis species: physiological analysis, expression profiles and function verification - Hao Zhang; Changhua Jiang; Rui Wang; Long Zhang; Ruonan Gai; Siyuan Peng; Yi Zhang; Chanjuan Mao; Yuxia Lou; Jianbin Mo; Shucheng Feng; Feng Ming (Plant Molecular Biology, 2021)

Comparison of different sampling strategies for debris flow susceptibility mapping: A case study using the centroids of the scarp area, flowing area and accumulation area of debris flow watersheds - Rui-yuan Gao; Chang-ming Wang; Zhu Liang (Journal of Mountain Science, 2021)

Composition and co-occurrence patterns of Phragmites australis rhizosphere bacterial community - Siwen Hu; Rujia He; Wanjie Wang; Dayong Zhao; Jin Zeng; Rui Huang; Ming Duan; Zhongbo Yu (Aquatic Ecology, 2021)

Research on fault recognition method combining 3D Res-UNet and knowledge distillation - Jing Wang; Jun-Hua Zhang; Jia-Liang Zhang; Feng-Ming Lu; Rui-Gang Meng; Zuoqian Wang (Applied Geophysics, 2021)

Geochemistry and zircon U-Pb ages of the Oligocene sediments in the Baiyun Sag, Zhujiang River Mouth Basin - Rui Sun; Ming Ma; Kai Zhong; Xiayang Wang; Zhao Zhao; Shuai Guo; Xingzong Yao; Gongcheng Zhang (Acta Oceanologica Sinica, 2021)

Astrocyte-Derived Lactate Modulates the Passive Coping Response to Behavioral Challenge in Male Mice - Ya-Nan Yin; Jian Hu; Yi-Li Wei; Ze-Lin Li; Zhou-Cai Luo; Rui-Qi Wang; Ke-Xin Yang; Shu-Ji Li; Xiao-Wen Li; Jian-Ming Yang; Tian-Ming Gao (Neuroscience Bulletin, 2021)

Isoorientin exerts a urate-lowering effect through inhibition of xanthine oxidase and regulation of the TLR4-NLRP3 inflammasome signaling pathway - Meng-Fei An; Ming-Yue Wang; Chang Shen; Ze-Rui Sun; Yun-Li Zhao; Xuan-Jun Wang; Jun Sheng (Journal of Natural Medicines, 2021)

Light grazing facilitates carbon accumulation in subsoil in Chinese grasslands: A meta‐analysis - Zhi‐Yun Jiang; Zhong‐Min Hu; Derrick Y. F. Lai; Dao‐Rui Han; Mei Wang; Min Liu; Meng Zhang; Ming‐Yan Guo (Global Change Biology, 2020)
Grazing by livestock greatly affects the soil carbon (C) cycle in grassland ecosystems. However, the effects of grazing at different intensities and durations on the dynamics of soil C in its subsoil layers are not clearly understood. Here, we compiled data from 78 sites (in total 122 published studies) to examine the effects of varying grazing intensities and durations on soil C content at different depths for grasslands in China. Our meta‐analysis revealed that grazing led to an overall decrease in soil C content and productivity of above‐ground vegetation (e.g., above‐ground biomass and litter) but an increase in below‐ground biomass. Specifically, the effects of grazing on soil C content became less negative or even positive with increasing soil depths. An increase of soil C content was consequently found under light grazing (LG), although soil C content still decreased under moderate and heavy grazing. The increase in soil C content under LG could be largely attributed to the increase of soil C content in subsoil layers (>20 cm), despite that soil C content in surface soil layer (0–20 cm) decreased. Moreover, the magnitude of increase in soil C content under LG in subsoil layers increased with grazing duration. A possible reason of the increase in soil C content in the subsoil layers was due to the increases in below‐ground biomass. Our study highlights that LG may modify the allocation of C input and promote its accumulation in subsoil layers, thus offsetting the negative impact of grazing on surface soil C content, a finding that has significant implications for C sequestration in grasslands.

Hydrogeochemical and isotopic characteristics of groundwater in Xinchang preselected site and their implications - Zhichao Zhou; Ju Wang; Rui Su; Yonghai Guo; Jingbo Zhao; Ming Zhang; Ruili Ji; Yanan Li; Jiebiao Li (Environmental Science and Pollution Research, 2020)

Distribution and risk of mercury in the sediments of mangroves along South China Coast - Rui-Fei Ma; Hao Cheng; Aniefiok Inyang; Ming Wang; You-Shao Wang (Ecotoxicology, 2020)

Spatial Variation in Thermal Stress Experienced by Barnacles on Rocky Shores: The Interplay Between Geographic Variation, Tidal Cycles and Microhabitat Temperatures - Hui-Yu Wang; Ling Ming Tsang; Fernando P. Lima; Rui Seabra; Monthon Ganmanee; Gray A. Williams; Benny K. K. Chan (Frontiers in Marine Science, 2020)

The role of miRNA-155 in monocrotaline-induced pulmonary arterial hypertension through c-Fos/NLRP3/caspase-1 - Shou-Dong Chai; Zhen-Kun Li; Rui Liu; Tao Liu; Ming-Feng Dong; Pei-Zhe Tang; Jian-Tang Wang; Sheng-Jun Ma (Molecular & Cellular Toxicology, 2020)

Drought characteristics and its impact on changes in surface vegetation from 1981 to 2015 in the Yangtze River Basin, China - Weixia Jiang; Lunche Wang; Lan Feng; Ming Zhang; Rui Yao (International Journal of Climatology, 2020)
Located in the subtropical monsoon climate area of China, the Yangtze River Basin (YRB) had been frequently affected by drought events recently. Based on standardized precipitation evapotranspiration Index (SPEI) and enhanced vegetation index (EVI), the characteristics of drought in the YRB and the influence of drought on vegetation in different seasons were investigated by maximum correlation ( R max ) between 1981 and 2015. The results showed that: (a) Droughts occurred frequently but had no obvious regularity in the YRB from 1981 to 2015. The drought intensity in autumn and winter were slightly higher than that in spring and summer. The autumn droughts in Sichuan Basin were the most serious, followed by the spring droughts in the middle and lower reaches of the YRB; (b) Annual SPEI series at 102 stations exhibited a downward trend and 72 stations exhibited an upward trend. There was no station showing a significant downward trend and two stations showing a significant upward trend. There was a drying trend in autumn and winter, and a wetting trend in spring and summer. The eastern area of the YRB shows a more arid trend in spring and autumn, as well as in the southwest in winter; (c) 90% of YRB showed a significant positive correlation ( p

Mapping and characterization of major QTL for spike traits in common wheat - Cheng-Hao Kuang; Xiao-Fang Zhao; Ke Yang; Zhi-Peng Zhang; Li Ding; Zhi-En Pu; Jian Ma; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng; et al. (Physiology and Molecular Biology of Plants, 2020)

Characterization of a Rapeseed Anthocyanin-More Mutant with Enhanced Resistance to Sclerotinia sclerotiorum - Rui Liu; Li-Na Ding; Ming Li; Wei Cao; Yu-Kang Wang; Wei-Jie Wang; Yan-Kun Yu; Zheng Wang; Ke-Ming Zhu; Xiao-Li Tan (Journal of Plant Growth Regulation, 2020)

Clinical strategies for differentiating IgG4-related cholecystitis from gallbladder carcinoma to avoid unnecessary surgical resection - Rui Zhang; Hao-Ming Lin; Zhao-Xi Cai; Su-Juan Du; Hong Zeng; Lei-Bo Xu; Jie Wang; Chao Liu (Science China Life Sciences, 2020)

Uptake and accumulation of pentachloronitrobenzene in pak choi and the human health risk - Ming Li; Guanghui Xu; Rui Yu; Yang Wang; Yong Yu (Environmental Geochemistry and Health, 2020)

Preparation and In vitro Evaluation of FDM 3D-Printed Ellipsoid-Shaped Gastric Floating Tablets with Low Infill Percentages - Di Chen; Xiang-Yu Xu; Rui Li; Gen-Ao Zang; Yue Zhang; Ming-Rui Wang; Meng-Fei Xiong; Jia-Rui Xu; Ting Wang; Hui Fu; Qin Hu; Bin Wu; et al. (AAPS PharmSciTech, 2020)

Specimen shape and cross-section effects on the mechanical properties of rocks under uniaxial compressive stress - Kun Du; Rui Su; Ming Tao; Chengzhi Yang; Aliakbar Momeni; Shaofeng Wang (Bulletin of Engineering Geology and the Environment, 2019)

RETRACTED ARTICLE: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2019)

Material Flow and Spatial Data Analysis of the Petroleum Use to Carbon Dioxide (CO 2 ) Emissions in Northeast China - Guang‐xin Liu; Ming Wu; Feng‐rui Jia; Qiang Yue; He‐ming Wang (Journal of Industrial Ecology, 2019)
Summary This study investigated the petroleum consumption and petroleum‐related CO 2 emissions (PCOEs) in Northeast China at city level using material flow analysis (MFA) and spatial data analysis (SDA). The petroleum flows for the year 2014 were plotted, and then the spatial patterns, weighted mean centers (WMCs), and spatial autocorrelations of petroleum consumption and PCOEs were calculated, respectively. It was found that Northeast China is a petroleum exploitation‐processing‐export region in China; the total input of petroleum flows comprised two parts—exploitation (about 60%) and import (about 40%). About one third of the total product oil supply flowed into other provinces. In the consumption process, the product oil was dominated by two sectors: the industry sector (45.5%) and the transportation sector (31%). The rate of PCOEs was 36.69 million tonnes in the waste discharge process. Meanwhile, the WMCs of the petroleum consumption and the PCOEs were located in the south of Northeast China. The location of the petroleum pipelines was the factor shown to determine the spatial patterns of petroleum consumption and PCOEs and the hotspots were distributed along the petroleum pipeline, especially in the Circum‐Bohai Sea regions. Economic development in these regions shows a positive dependence on petroleum consumption and generates larger PCOEs. The findings obtained in this study could provide important decision‐making support to low‐carbon development in Northeast China.

Nanoparticles: Oral Delivery for Protein and Peptide Drugs - Shu-jun Cao; Shuo Xu; Hui-ming Wang; Yong Ling; Jiahua Dong; Rui-dong Xia; Xiang-hong Sun (AAPS PharmSciTech, 2019)

Identification of the complete mitochondrial genome of Garra pingi pingi (Cypriniformes, Cyprinidae) - Yuan-Chao Zou; Mei Chen; Chuan-Jie Qin; Yong-Ming Wang; Rui Li; Ze-Min Qi; Zheng-Yong Wen (Conservation Genetics Resources, 2018)

Acupuncture Prevents the Impairment of Hippocampal LTP Through β1-AR in Vascular Dementia Rats - Ling-Yong Xiao; Xue-Rui Wang; Jing-Wen Yang; Yang Ye; Wen Zhu; Yan Cao; Si-Ming Ma; Cun-Zhi Liu (Molecular Neurobiology, 2018)

Lappaconitine, a C18-diterpenoid alkaloid, exhibits antihypersensitivity in chronic pain through stimulation of spinal dynorphin A expression - Ming-Li Sun; Jun-Ping Ao; Yi-Rui Wang; Qian Huang; Teng-Fei Li; Xin-Yan Li; Yong-Xiang Wang (Psychopharmacology, 2018)

Use of cationic microbubbles targeted to P-selectin to improve ultrasound-mediated gene transfection of hVEGF165 to the ischemic myocardium - Wei-hui Shentu; Cao-xin Yan; Chun-mei Liu; Rui-xiang Qi; Yao Wang; Zhao-xu Huang; Li-ming Zhou; Xiang-dong You (Journal of Zhejiang University-SCIENCE B, 2018)

Precipitation characteristics over the steep slope of the Himalayas in rainy season observed by TRMM PR and VIRS - Yunfei Fu; Xiao Pan; Tao Xian; Guosheng Liu; Lei Zhong; Qi Liu; Rui Li; Yu Wang; Ming Ma (Climate Dynamics, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Spatial trends and pollution assessment for mercury in the surface soils of the Nansi Lake catchment, China - Ming-Yi Ren; Li-Yuan Yang; Long-Feng Wang; Xue-mei Han; Jie-Rui Dai; Xu-Gui Pang (Environmental Science and Pollution Research, 2018)

Synthesis and biological evaluation of disulfides bearing 1,2,4-triazole moiety as antiproliferative agents - Xue-Feng Wang; Shuai Zhang; Bao-Lin Li; Ji-Jun Zhao; Yu-Ming Liu; Rui-Lian Zhang; Bo Li; Bao-Quan Chen (Medicinal Chemistry Research, 2017)

Isolation and complete genome sequence of Halorientalis hydrocarbonoclasticus sp. nov., a hydrocarbon-degrading haloarchaeon - Dahe Zhao; Sumit Kumar; Jian Zhou; Rui Wang; Ming Li; Hua Xiang (Extremophiles, 2017)

Expression-based genotyping of the rice blast resistance genes in the elite maintainer line Yixiang1B - Li Wang; Xiao-Hong Hu; Gang Lin; De-Ming Zhao; Jun Shi; Zhi-Xue Zhao; Rui Zeng; Heng-Jing Li; De-Qiang Li; Jing Fan; Yan Li; Fu Huang; et al. (European Journal of Plant Pathology, 2017)

Occurrence and profiles of polybrominated diphenyl ethers (PBDEs) in riverine sediments of Shanghai: a combinative study with human serum from the locals - Ming-Hong Wu; Ben-Tuo Xu; Gang Xu; Ming-Nan Wang; Jing Ma; Chen-Yuan Pan; Rui Sun; Tao Han; Liang Tang (Environmental Geochemistry and Health, 2017)

A simple method for removing low-density granulocytes to purify T lymphocytes from peripheral blood mononuclear cells - Si-gong Zhang; Yu-xin Song; Xiao-ming Shu; Hai-li Shen; Han-bo Yang; Rui-xue Duo; Guo-chun Wang (Journal of Zhejiang University-SCIENCE B, 2017)

The complete mitochondrial genome of a threatened loach (Sinibotia reevesae) and its phylogeny - Yuan-Chao Zou; Bi-Wen Xie; Chuan-Jie Qin; Yong-Ming Wang; Deng-Yue Yuan; Rui Li; Zheng-Yong Wen (Genes & Genomics, 2017)

Erratum to: Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling‑Ling Zhang; Hu Chen; Mi Luo; Xiao‑Wei Zhang; Mei Deng; Jian Ma; Peng‑Fei Qi; Ji‑Rui Wang; Guo‑Yue Chen; Ya‑Xi Liu; Zhi‑En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling-Ling Zhang; Hu Chen; Mi Luo; Xiao-Wei Zhang; Mei Deng; Jian Ma; Peng-Fei Qi; Ji-Rui Wang; Guo-Yue Chen; Ya-Xi Liu; Zhi-En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

The Research on the Relationship of RAGE, LRP-1, and Aβ Accumulation in the Hippocampus, Prefrontal Lobe, and Amygdala of STZ-Induced Diabetic Rats - Lou-Yan Ma; Yu-Lang Fei; Xiao-Ye Wang; Song-Di Wu; Jun-Hui Du; Mei Zhu; Long Jin; Ming Li; Hai-Long Li; Jia-Jia Zhai; Lu-Peng Ji; Ran-Ran Ma; et al. (Journal of Molecular Neuroscience, 2017)

Land use legacies and nitrogen fertilization affect methane emissions in the early years of rice field development - Rui Shao; Ming Xu; Renqiang Li; Xiaoqin Dai; Lixiang Liu; Ye Yuan; Huimin Wang; Fengting Yang (Nutrient Cycling in Agroecosystems, 2017)

Oxygen microprofiles within the sediment-water interface studied by optode and its implication for aeration of polluted urban rivers - Bo Liu; Rui-ming Han; Wen-lin Wang; Hong Yao; Feng Zhou (Environmental Science and Pollution Research, 2017)

IP-10/CXCR3 Axis Promotes the Proliferation of Vascular Smooth Muscle Cells through ERK1/2/CREB Signaling Pathway - Hui-jin Wang; Yu Zhou; Rui-ming Liu; Yuan-sen Qin; Ying-huan Cen; Ling-yu Hu; Shen-ming Wang; Zuo-jun Hu (Cell Biochemistry and Biophysics, 2017)

Blood Flow and Oxygen Transport in Descending Branch of Lateral Femoral Circumflex Arteries After Transfemoral Amputation: A Numerical Study - Fei Yan; Wen-Tao Jiang; Rui-Qi Dong; Qing-Yuan Wang; Yu-Bo Fan; Ming Zhang (Journal of Medical and Biological Engineering, 2017)

MicroRNA-146a Promotes Oligodendrogenesis in Stroke - Xian Shuang Liu; Michael Chopp; Wan Long Pan; Xin Li Wang; Bao Yan Fan; Yi Zhang; Haifa Kassis; Rui Lan Zhang; Xiao Ming Zhang; Zheng Gang Zhang (Molecular Neurobiology, 2017)

Sugar Industry and Improved Sugarcane Farming Technologies in China - Yang-Rui Li; Xiu-Peng Song; Jian-Ming Wu; Chang-Ning Li; Qiang Liang; Xi-Hui Liu; Wei-Zan Wang; Hong-Wei Tan; Li-Tao Yang (Sugar Tech, 2016)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Characterization and expression analyses of the H+-pyrophosphatase gene in rye - CHANG-SHUI WANG; QIAN-TAO JIANG; JIAN MA; XIU-YING WANG; JI-RUI WANG; GUO-YUE CHEN; PENG-FEI QI; YUAN-YING PENG; XIU-JIN LAN; YOU-LIANG ZHENG; YU-MING WEI (Journal of Genetics, 2016)

Lead Exposure Impairs Hippocampus Related Learning and Memory by Altering Synaptic Plasticity and Morphology During Juvenile Period - Tao Wang; Rui-Li Guan; Ming-Chao Liu; Xue-Feng Shen; Jing Yuan Chen; Ming-Gao Zhao; Wen-Jing Luo (Molecular Neurobiology, 2016)

Characterization of the waxy gene in diploid Triticum L. and Aegilops L. species and its geographic distribution - Wei Li; Bang-Bo Fu; Zhe Li; Ya-Xi Liu; Zhi-En Pu; Peng-Fei Qi; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng (Genetic Resources and Crop Evolution, 2016)

Effects of climate change on potential habitats of the cold temperate coniferous forest in Yunnan province, southwestern China - Wang-jun Li; Ming-chun Peng; Motoki Higa; Nobuyuki Tanaka; Tetsuya Matsui; Cindy Q. Tang; Xiao-kun Ou; Rui-wu Zhou; Chong-yun Wang; Hai-zhong Yan (Journal of Mountain Science, 2016)

Inoculation of Fe/Mn-oxidizing bacteria enhances Fe/Mn plaque formation and reduces Cd and As accumulation in Rice Plant tissues - Ming Fang Dong; Ren Wei Feng; Rui Gang Wang; Yang Sun; Yong Zhen Ding; Ying Ming Xu; Zhi Lian Fan; Jun Kang Guo (Plant and Soil, 2016)

Submerged macrophytes shape the abundance and diversity of bacterial denitrifiers in bacterioplankton and epiphyton in the Shallow Fresh Lake Taihu, China - Zhou Fan; Rui-ming Han; Jie Ma; Guo-xiang Wang (Environmental Science and Pollution Research, 2016)

Dynamics of Dissolved Oxygen and the Affecting Factors in Sediment of Polluted Urban Rivers under Aeration Treatment - Bo Liu; Wen-lin Wang; Rui-ming Han; Ming Sheng; Lin-lin Ye; Xu Du; Xin-ting Wu; Guo-xiang Wang (Water, Air, & Soil Pollution, 2016)

Re: “PICALM Gene rs3851179 Polymorphism Contributes to Alzheimer’s Disease in an Asian Population” - Ming-Jie Wang; Rui-Ping Liu; Zhi-Jun Kong (NeuroMolecular Medicine, 2016)

Structure and expression of phosphoglucan phosphatase genes of Like Sex Four1 and Like Sex Four2 in barley - Jian Ma; Shang Gao; Qian-Tao Jiang; Qiang Yang; Min Sun; Ji-Rui Wang; Peng-Fei Qi; Ya-Xi Liu; Wei Li; Zhi-En Pu; Xiu-Jin Lan; Yu-Ming Wei; et al. (Genetica, 2016)

Optimization of operation conditions for the mitigation of nitrous oxide (N2O) emissions from aerobic nitrifying granular sludge system - Rui-Ting Liu; Xin-Hua Wang; Yan Zhang; Ming-Yu Wang; Ming-Ming Gao; Shu-Guang Wang (Environmental Science and Pollution Research, 2016)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Inhibition of IRF3 expression reduces TGF-β1-induced proliferation of hepatic stellate cells - Ming-ming Ni; Tao Xu; Ya-rui Wang; Ying-hua He; Qun Zhou; Cheng Huang; Xiao-ming Meng; Jun Li (Journal of Physiology and Biochemistry, 2016)

Antimicrobial activity of human β-defensins against lactic acid bacteria - Xiao-Fang Wang; Fei Tian; Rui-Ming Cao; Jing Li; Sheng-Mei Wu; Xiao-Kui Guo; Tong-Xin Chen (Natural Product Research, 2015)

Effect of hydrogen sulfide on D1 protein in wheat under drought stress - Hua Li; Ming Quan Gao; Rui Li Xue; Dan Wang; Hui Jie Zhao (Acta Physiologiae Plantarum, 2015)

Characterization of genes encoding Starch Branching Enzyme I from Triticum monococcum and its diploid wheat relatives - Xiu-Ying Wang; Chang-Shui Wang; Jian Ma; Ji-Rui Wang; Ya-Xi Liu; Peng-Fei Qi; Wei Li; Zhi-En Pu; Xiu-Jin Lan; Yu-Ming Wei; You-Liang Zheng; Qian-Tao Jiang (Biologia, 2015)

Activation of VEGF/Flk-1-ERK Pathway Induced Blood–Brain Barrier Injury After Microwave Exposure - Li-Feng Wang; Xiang Li; Ya-Bing Gao; Shui-Ming Wang; Li Zhao; Ji Dong; Bin-Wei Yao; Xin-Ping Xu; Gong-Min Chang; Hong-Mei Zhou; Xiang-Jun Hu; Rui-Yun Peng (Molecular Neurobiology, 2015)

Quantitative trait locus mapping for seed dormancy in different post-ripening stages in a Tibetan semi-wild wheat (Triticum aestivum ssp. tibetanum Shao) - Yun-Feng Jiang; Ji-Rui Wang; Wei Luo; Yu-Ming Wei; Peng-Fei Qi; Ya-Xi Liu; Qian-Tao Jiang; Yuan-Ying Peng; Guo-Yue Chen; Shou-Fen Dai; You-Liang Zheng; Xiu-Jin Lan (Euphytica, 2015)

Review and evaluation of China’s standards and regulations on the fuel consumption of motor vehicles - Yue-Fu Jin; Zhao Wang; Hui-Ming Gong; Tian-Lei Zheng; Xiang Bao; Jia-Rui Fan; Michael Wang; Miao Guo (Mitigation and Adaptation Strategies for Global Change, 2015)

Mineralogy and isotope geochemical characteristics for Xiaozhen copper deposit, Langao County, Shaanxi Province and their constraint on genesis of the deposit - Gang Wang; Zong-qi Wang; Rui Shi; Ying-li Zhang; Kun-ming Wang (Geosciences Journal, 2015)

Burkholderia metalliresistens sp. nov., a multiple metal-resistant and phosphate-solubilising species isolated from heavy metal-polluted soil in Southeast China - Jun Kang Guo; Yong Zhen Ding; Ren Wei Feng; Rui Gang Wang; Ying Ming Xu; Chun Chen; Xiu Li Wei; Wei Min Chen (Antonie van Leeuwenhoek, 2015)

Molecular Cloning and Functional Analysis of an Ethylene Receptor Gene from Sugarcane (Saccharum spp.) by Hormone and Environmental Stresses - Ai-Qin Wang; Xing-Zhi Ye; Jing-Li Huang; Jun-Qi Niu; Ming Liu; Yong-Bao Pan; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2015)

Anxiolytic effects of ketamine in animal models of posttraumatic stress disorder - Li-Ming Zhang; Wen-Wen Zhou; Ya-Jun Ji; Ying Li; Nan Zhao; Hong-Xia Chen; Rui Xue; Xin-Guo Mei; You-Zhi Zhang; Heng-Lin Wang; Yun-Feng Li (Psychopharmacology, 2015)

Upregulation of HIF-1α Via Activation of ERK and PI3K Pathway Mediated Protective Response to Microwave-Induced Mitochondrial Injury in Neuron-Like Cells - Li Zhao; Yue-Feng Yang; Ya-Bing Gao; Shui-Ming Wang; Li-Feng Wang; Hong-Yan Zuo; Ji Dong; Xin-Ping Xu; Zhen-Tao Su; Hong-Mei Zhou; Ling-Ling Zhu; Rui-Yun Peng (Molecular Neurobiology, 2014)

Needle-free injection of insulin powder: delivery efficiency and skin irritation assessment - Chun-yu Li; Zhe-wei Wang; Can Tu; Jia-bo Wang; Bing-qian Jiang; Qi Li; Ling-na Zeng; Zhi-jie Ma; Ping Zhang; Yan-ling Zhao; Ya-ming Zhang; Dan Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Two new compounds from a marine-derived fungus Penicillium oxalicum - Pei-Le Wang; Dan-Yi Li; Lei-Rui Xie; Xin Wu; Hui-Ming Hua; Zhan-Lin Li (Natural Product Research, 2014)

Plant diversity as a good indicator of vegetation stability in a typical plateau wetland - Wei Li; Rui Tan; Yu-ming Yang; Juan Wang (Journal of Mountain Science, 2014)

Cloning and expression patterns of the brine shrimp (Artemia sinica) glycogen phosphorylase (GPase) gene during development and in response to temperature stress - Na Zhao; Ming Hou; Ting Wang; Yifei Chen; Ying Lv; Zengrong Li; Rui Zhang; Wenting Xin; Xiangyang Zou; Lin Hou (Molecular Biology Reports, 2014)

Effects of submerged macrophytes on the abundance and community composition of ammonia-oxidizing prokaryotes in a eutrophic lake - Da-yong Zhao; Juan Luo; Jin Zeng; Meng Wang; Wen-ming Yan; Rui Huang; Qinglong L. Wu (Environmental Science and Pollution Research, 2014)

Potato leafroll virus (PLRV) and Potato virus Y (PVY) influence vegetative growth, physiological metabolism, and microtuber production of in vitro-grown shoots of potato (Solanum tuberosum L.) - Jing-Wei Li; Biao Wang; Xiao-Ming Song; Ren-Rui Wang; Long Chen; Hao Zhang; Zhi-Bo Zhang; Qiao-Chun Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

In vitro mutagenesis and directed screening for salt-tolerant mutants in peanut - Ming-Xia Zhao; Hai-Yan Sun; Rui-Rui Ji; Xiao-Hui Hu; Jiong-Ming Sui; Li-Xian Qiao; Jing Chen; Jing-Shan Wang (Euphytica, 2013)

Priming of Anti-Herbivore Defense in Tomato by Arbuscular Mycorrhizal Fungus and Involvement of the Jasmonate Pathway - Yuan Yuan Song; Mao Ye; Chuan You Li; Rui Long Wang; Xiao Chen Wei; Shi Ming Luo; Ren Sen Zeng (Journal of Chemical Ecology, 2013)

Effects of Ethephon on Key Enzymes of Sucrose Metabolism in Relation to Sucrose Accumulation in Sugarcane - Ai-Qin Wang; Wen-Jing Huang; Jun-Qi Niu; Ming Liu; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2013)

Meso-Cenozoic extensional structures in the Northern Tarim Basin, NW China - Yue-Jun Li; Yan Zhao; Long-De Sun; Wen-Jie Song; Duo-Ming Zheng; Ya-Lei Liu; Dao-Xuan Wang; Jian-Feng Hu; Qi-Rui Zhang (International Journal of Earth Sciences, 2013)

A new cyclonerol derivative from a marine-derived fungus Ascotricha sp. ZJ-M-5 - Lei-Rui Xie; Dan-Yi Li; Zhan-Lin Li; Hui-Ming Hua; Pei-Le Wang; Xin Wu (Natural Product Research, 2013)

Protective effect of hydrogen-rich saline on ischemia/reperfusion injury in rat skin flap - Ling Zhao; You-bin Wang; Shi-rui Qin; Xue-mei Ma; Xue-jun Sun; Ming-lian Wang; Ru-gang Zhong (Journal of Zhejiang University-SCIENCE B, 2013)

Identification of 40k γ-secalin genes - PENG-FEI QI; QING CHEN; THÉRÈSE OUELLET; CHENG-XING LE; JIA AI; YU-MING WEI; JI-RUI WANG; YOU-LIANG ZHENG (Journal of Genetics, 2013)

The effects of three years of fencing enclosure on soil seed banks and the relationship with above-ground vegetation of degraded alpine grasslands of the Tibetan plateau - Zhan-Huan Shang; Bin Deng; Lu-Ming Ding; Guo-Hua Ren; Guo-Sheng Xin; Zhi-Yun Liu; Yan-Long Wang; Rui-Jun Long (Plant and Soil, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Arbuscular mycorrhizal fungal diversity, external mycelium length, and glomalin-related soil protein content in response to long-term fertilizer management - Jue Dai; Junli Hu; Xiangui Lin; Anna Yang; Rui Wang; Jiabao Zhang; Ming Hung Wong (Journal of Soils and Sediments, 2013)

Isolation and characterization of a stress responsive small GTP-binding protein AhRabG3b in peanut (Arachis hypogaea L.) - Jiong-Ming Sui; Rui Li; Qian-Cheng Fan; Lin Song; Chun-Hua Zheng; Jing-Shan Wang; Li-Xian Qiao; Shan-Lin Yu (Euphytica, 2013)

Meta-analysis of QTL associated with tolerance to abiotic stresses in barley - Wei-Tao Li; Chunji Liu; Ya-Xi Liu; Zhi-En Pu; Shou-Fen Dai; Ji-Rui Wang; Xiu-Jin Lan; You-Liang Zheng; Yu-Ming Wei (Euphytica, 2013)

CSMD1 exhibits antitumor activity in A375 melanoma cells through activation of the Smad pathway - Ming-Rui Tang; Yu-Xin Wang; Shu Guo; Si-Yuan Han; Di Wang (Apoptosis, 2012)

Involvement of p38MAPK/NF-κB Signaling Pathways in Osteoblasts Differentiation in Response to Mechanical Stretch - Liang Wang; Jian-yu Li; Xi-zheng Zhang; Lu Liu; Zong-ming Wan; Rui-xin Li; Yong Guo (Annals of Biomedical Engineering, 2012)

Effects of flue gas desulfurization gypsum by-products on microbial biomass and community structure in alkaline–saline soils - Ming Li; Lili Jiang; Zhaojun Sun; Jinzhi Wang; Yichao Rui; Lei Zhong; Yanfen Wang; Paul Kardol (Journal of Soils and Sediments, 2012)

Synthesis of 2-R1-2-(4-(2-fluoroethoxy)benzamido)acetate as potential PET imaging agents - Yong He; Jingli Xu; Hang Liu; Man Feng; Xiao Wang; Rui Ding; Chuanmin Qi; Yurong Chen; Fang Li; Zhao-Hui Zhu; Yong-Hong Dang; Ming Wang; et al. (Medicinal Chemistry Research, 2012)

Dynamics and functions of CD4+CD25high regulatory T lymphocytes in Chinese rhesus macaques during the early stage of infection with SIVmac239 - Shao-You Li; Hou-Jun Xia; Zheng-Xi Dai; Gao-Hong Zhang; Bo Fan; Ming-Hua Li; Rui-Rui Wang; Yong-Tang Zheng (Archives of Virology, 2012)

Induction of DIMBOA accumulation and systemic defense responses as a mechanism of enhanced resistance of mycorrhizal corn (Zea mays L.) to sheath blight - Yuan Yuan Song; Man Cao; Li Jun Xie; Xiao Ting Liang; Ren Sen Zeng; Yi Juan Su; Jing Hua Huang; Rui Long Wang; Shi Ming Luo (Mycorrhiza, 2011)

Olig1 and ID4 interactions in living cells visualized by bimolecular fluorescence complementation technique - Shu-Jun Guo; Jian-Guo Hu; Bao-Ming Zhao; Lin Shen; Rui Wang; Jian-Sheng Zhou; He-Zuo Lü (Molecular Biology Reports, 2011)

Identification of a Novel Bacterial K+ Channel - Guanghua Tang; Bo Jiang; Yuan Huang; Ming Fu; Lingyun Wu; Rui Wang (The Journal of Membrane Biology, 2011)

Artesunate inhibits growth and induces apoptosis in human osteosarcoma HOS cell line in vitro and in vivo - Qiang Xu; Zhao-xu Li; Hui-qin Peng; Zheng-wang Sun; Rui-lin Cheng; Zhao-ming Ye; Wei-xu Li (Journal of Zhejiang University-SCIENCE B, 2011)

Cytosolic PrP Induces Apoptosis of Cell by Disrupting Microtubule Assembly - Xiao-Li Li; Gui-Rong Wang; Yuan-Yuan Jing; Ming-Ming Pan; Chen-Fang Dong; Rui-Min Zhou; Zhao-Yun Wang; Qi Shi; Chen Gao; Xiao-Ping Dong (Journal of Molecular Neuroscience, 2011)

Evaluation of Genetic Manipulation Strategies on d-Lactate Production by Escherichia coli - Li Zhou; Zhi-Rui Zuo; Xian-Zhong Chen; Dan-Dan Niu; Kang-Ming Tian; Bernard A. Prior; Wei Shen; Gui-Yang Shi; Suren Singh; Zheng-Xiang Wang (Current Microbiology, 2011)

Molecular phylogeny of Ranunculaceae based on rbc L sequences - Ying-fan Cai; Sheng-wei Li; Min Chen; Ming-feng Jiang; Yi Liu; Yong-fang Xie; Quan Sun; Huai-zhong Jiang; Neng-wen Yin; Ling Wang; Rui Zhang; Cheng-lin Huang; et al. (Biologia, 2010)

Preliminary study on the freeze-drying of human bone marrow-derived mesenchymal stem cells - Shao-zhi Zhang; Huan Qian; Zhen Wang; Ju-li Fan; Qian Zhou; Guang-ming Chen; Rui Li; Shan Fu; Jie Sun (Journal of Zhejiang University-SCIENCE B, 2010)

Genome-wide identification and evaluation of novel internal control genes for Q-PCR based transcript normalization in wheat - Xiang-Yu Long; Ji-Rui Wang; Thérèse Ouellet; Hélène Rocheleau; Yu-Ming Wei; Zhi-En Pu; Qian-Tao Jiang; Xiu-Jing Lan; You-Liang Zheng (Plant Molecular Biology, 2010)

Identification, localization, and characterization of putative USP genes in barley - Wei-Tao Li; Yu-Ming Wei; Ji-Rui Wang; Chun-Ji Liu; Xiu-Jin Lan; Qian-Tao Jiang; Zhi-En Pu; You-Liang Zheng (Theoretical and Applied Genetics, 2010)

Isolation and characterization of microsatellite markers from Lagerstroemia caudata (Lythraceae) and cross-amplification in other related species - Ming Cai; Rui Meng; Hui-Tang Pan; Yi-Ke Gao; Ming Sun; Ping Song; Xue-Feng Wang; Qi-Xiang Zhang (Conservation Genetics Resources, 2010)

Neural circuits and temporal plasticity in hindlimb representation of rat primary somatosensory cortex: revisited by multi-electrode array on brain slices - Dan-Dan Wang; Zhen Li; Ying Chang; Rui-Rui Wang; Xue-Feng Chen; Zhen-Yu Zhao; Fa-Le Cao; Jian-Hui Jin; Ming-Gang Liu; Jun Chen (Neuroscience Bulletin, 2010)

Sequence and expression analysis of the gene encoding inducible cAMP early repressor in tilapia - Ming Chen; Rui Wang; Xi Gan; Aiying Lei; Chao Li; Xiaoli Yu; Jun Huang; Ting Huang; Wanwen Liang (Molecular Biology Reports, 2010)

Research development of the pathogenesis pathways for neuroschistosomiasis - Peng Wang; Ming-Can Wu; Shi-Jie Chen; Guo-Cai Luo; Xiang-Ling Cheng; Zhan-Sheng Zhu; Guang-Rui Zhao (Neuroscience Bulletin, 2010)

Molecular diversity and phylogenetic analyses of y-type high-molecular-weight glutenin promoters from different genomes in Triticeae - Qian-Tao Jiang; Yu-Ming Wei; Ji-Rui Wang; Ze-Hong Yan; You-Liang Zheng (Plant Systematics and Evolution, 2010)

Inhibitor of DNA binding-1 promotes the migration and proliferation of endothelial progenitor cells in vitro - Hong Wang; Yang Yu; Rui-wei Guo; Yan-kun Shi; Ming-bao Song; Jian-fei Chen; Shi-yong Yu; Yang-guang Yin; Pan Gao; Lan Huang (Molecular and Cellular Biochemistry, 2010)

A new iridoid glycoside from Scrophularia ningpoensis - Zheng-Rui Niu; Ru-Feng Wang; Ming-Ying Shang; Shao-Qing Cai (Natural Product Research, 2009)

Des-γ-carboxy prothrombin stimulates human vascular endothelial cell growth and migration - Su-Bo Wang; Yan-Na Cheng; Shu-Xiang Cui; Julia Li Zhong; S. G. Ward; Li-Rui Sun; Ming-Hui Chen; Norihiro Kokudo; Wei Tang; Xian-Jun Qu (Clinical & Experimental Metastasis, 2009)

Molecular Characterization of the pina Gene in Einkorn Wheat - Qing Chen; Peng-Fei Qi; Yu-Ming Wei; Ji-Rui Wang; You-Liang Zheng (Biochemical Genetics, 2009)

Infectivity and propagation of attenuated infectious bursal disease virus in the chicken B-lymphocyte cell line DT40 - Jun Luo; Gai-Ping Zhang; Jian-Ming Fan; Man Teng; Lei-Ming You; Ling Zhou; Rui-Guang Deng; Xuan-Nian Wang; Yan-Yan Yang; Li Wang; Guang-Xu Xing; Na Cheng (Archives of Virology, 2009)

QTL analysis of kernel shape and weight using recombinant inbred lines in wheat - Xian-Yin Sun; Ke Wu; Yan Zhao; Fan-Mei Kong; Guan-Zhu Han; Hong-Ming Jiang; Xing-Jiao Huang; Rui-Jun Li; Hong-Gang Wang; Si-Shen Li (Euphytica, 2009)

TRANSPARENT TESTA 12 genes from Brassica napus and parental species: cloning, evolution, and differential involvement in yellow seed trait - You-Rong Chai; Bo Lei; Hua-Lei Huang; Jia-Na Li; Jia-Ming Yin; Zhang-Lin Tang; Rui Wang; Li Chen (Molecular Genetics and Genomics, 2009)

Effects of ginkgolide B on neuronal discharges in paraventricular nucleus of rat hypothalamic slices - Yue Lin; Ru Wang; Xin Wang; Rui-Rong He; Yu-Ming Wu (Neuroscience Bulletin, 2008)

SNP and haplotype identification of the wheat monomeric α-amylase inhibitor genes - Ji-Rui Wang; Yu-Ming Wei; Ze-Hong Yan; You-Liang Zheng (Genetica, 2008)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.

Sequence Variations and Haplotype Identification of Wheat Dimeric α-Amylase Inhibitor Genes in Einkorn Wheats - Ji-Rui Wang; Yu-Ming Wei; Ze-Hong Yan; You-Liang Zheng (Biochemical Genetics, 2007)

Production and analysis of transgenic wheat (Triticum aestivum L.) with improved insect resistance by the introduction of cowpea trypsin inhibitor gene - Rui-Ming Bi; Hai-Yan Jia; De-Shun Feng; Hong-Gang Wang (Euphytica, 2006)

Genetic mapping of the wheat dimeric α-amylase inhibitor multi-gene family using allele-specific primers based on intergenomic SNPs - Ji-Rui Wang; Yu-Ming Wei; Ze-Hong Yan; You-Liang Zheng (Plant Molecular Biology Reporter, 2006)

Characterization of two HMW glutenin subunit genes from Taenitherum Nevski - Ze-Hong Yan; Yu-Ming Wei; Ji-Rui Wang; Deng-Cai Liu; Shou-Fen Dai; You-Liang Zheng (Genetica, 2006)

A high-molecular-weight glutenin subunit gene 1Dx2.1 from Xinjiang rice wheat - Qian-Tao Jiang; Yu-Ming Wei; Ji-Rui Wang; Ze-Hong Yan; You-Liang Zheng (Cereal Research Communications, 2005)

Fog- and Rainwater Chemistry in the Tropical Seasonal Rain Forest of Xishuangbanna, Southwest China - Wen Jie Liu; Yi Ping Zhang; Hong Mei Li; Fan Rui Meng; Yu Hong Liu; Chang-Ming Wang (Water, Air, & Soil Pollution, 2005)

Identification of a novel rice bZIP-type transcription factor gene,OsbZIP1, involved in response to infection ofMagnaporthe grisea - Xiang-Bing Meng; Wen-Sheng Zhao; Rui-Ming Lin; Min Wang; You-Liang Peng (Plant Molecular Biology Reporter, 2005)

Safety analysis of water resources and eco-environment in Shiyang River Basin - Ji-shi Zhang; Yong-qiu Zhang; Rui-feng Pu; Ren-sheng Chen; Zhong-shan Cheng; Ming-quan Wang (Chinese Geographical Science, 2005)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Genetic diversity in the Chinese pangolin (Manis pentadactyla) inferred from protein electrophoresis - Bing Su; Rui-Qing Liu; Ying-xiang Wang; Li-ming Shi (Biochemical Genetics, 1994)

Genetic diversity in the Chinese pangolin (Manis pentadactyla) inferred from protein electrophoresis - Bing Su; Rui-Qing Liu; Ying-xiang Wang; Li-ming Shi (Biochemical Genetics, 1994)